Ultraviolet curable adhesive composition, and method for producing multilayer body
Patent Information
- Application Number
- JP2024199151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-01
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-30
AI Technical Summary
【0125】 本発明によれば、酸素存在下における紫外線硬化性、防水·防塵性、及び、印刷後の形状安定性に優れる紫外線硬化型粘着剤組成物、並びに、酸素存在下において高照度の紫外線を照射した際の硬化性、硬化後の接着性及び保持性能に優れる紫外線硬化型粘着剤組成物を提供することができる。また、本発明によれば、該紫外線硬化型粘着剤組成物を用いてなる積層体の製造方法を提供することができる。
Smart Images

Figure 2025015663000001 
Figure 2025015663000002 
Figure 2025015663000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an ultraviolet-curable pressure-sensitive adhesive composition and a method for producing a laminate using the ultraviolet-curable pressure-sensitive adhesive composition. [Background technology]
[0002] Adhesives are used to bond electronic components inside electronic devices such as smartphones and PCs. In a typical method of bonding using adhesives, first, an adhesive sheet is prepared with separators arranged on both sides of the adhesive, and then the adhesive sheet is cut into a desired shape. Then, one separator is peeled off from the cut adhesive sheet, and one side of the exposed adhesive is bonded to a first adherend, and then the other separator is peeled off, and the other side of the exposed adhesive is bonded to a second adherend. In this method, a part of the adhesive sheet is discarded after cutting, resulting in waste.
[0003] In response to this, a method has been considered in which a pressure-sensitive adhesive composition is printed in a desired shape and then attached to an adherend without producing a pressure-sensitive adhesive sheet, which can reduce the generation of waste.
[0004] For example, Patent Document 1 discloses an invention for providing a radiation-curable pressure-sensitive adhesive composition that allows fine patterning and exhibits high adhesion to various adherends such as metals, plastics, etc. Patent Document 1 describes a radiation-curable pressure-sensitive adhesive composition that contains 10 to 70% by weight of an aromatic ring-free ethylenically unsaturated monomer, 1 to 10% by weight of a photopolymerization initiator, and 10 to 55% by weight of a crosslinking agent.
[0005] Patent Document 2 discloses an invention for providing a photocurable adhesive composition that, even when irradiated with light in the presence of oxygen, gives a laminate having adhesive strength equivalent to that in the absence of oxygen. Patent Document 2 describes a photocurable adhesive composition that contains (A) a (meth)acrylate oligomer, (B) a monofunctional (meth)acrylic monomer, (C) a difunctional to tetrafunctional (meth)acrylic monomer, (D) a photoinitiator, (E) a tackifier having a softening point of 70 to 150°C, and (F) a liquid plasticizer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-216742 A [Patent Document 2] International Publication No. 2016 / 163152 Summary of the Invention [Problem to be solved by the invention]
[0007] Tape is used to fix the housing of an electronic device, and the tape must be applied without gaps to prevent liquid and dust from entering the inside of the device. However, when forming a square shape along the periphery of a device with tape, there is a problem that the area of the inner squares becomes waste as it is. In contrast, there is a method of forming a square shape by combining multiple rectangular or L-shaped tapes, but it is difficult to fill the gaps between the tapes when applying them, and there is a problem that liquid and dust enter through the gaps. As described above, the generation of waste can be suppressed by the method of printing the adhesive composition in a desired shape and then laminating it to the adherend without preparing an adhesive sheet. On the other hand, as a method for curing the adhesive composition, ultraviolet curing is desirable to avoid heating the adherend, but in the conventional adhesive composition, in order to achieve both reactivity to ultraviolet light and adhesive properties, the amount of oxygen on the surface is reduced by placing it in a nitrogen atmosphere or laminating a film, and then the composition is cured by irradiating it with low-illuminance ultraviolet light so as to obtain a high cumulative light amount. Therefore, there are restrictions on equipment and production speed. In addition, there has been a problem in that the dimensions and shape of the adhesive composition may change after printing due to contact of the film with the uncured adhesive composition or application of heat in the drying process after printing. On the other hand, when curing is performed by irradiating ultraviolet light in the presence of oxygen such as in the atmosphere, there is a problem that the holding power decreases because the reaction rate differs between the front and back of the cured product. In addition, in recent years, ultraviolet light irradiation devices are being replaced by energy-saving UV-LEDs with a single wavelength from light sources with wide wavelength distributions such as high-pressure mercury lamps and metal halide lamps. However, with conventional pressure-sensitive adhesive compositions, there are problems in that it is difficult to sufficiently cure when irradiated with high-intensity ultraviolet light using a UV-LED in the presence of oxygen, or that sufficient adhesion is not obtained after curing.
[0008] The present invention aims to provide an ultraviolet-curable pressure-sensitive adhesive composition that is excellent in ultraviolet curability in the presence of oxygen, waterproofness and dust resistance, and shape stability after printing, and an ultraviolet-curable pressure-sensitive adhesive composition that is excellent in curability when irradiated with high-intensity ultraviolet light in the presence of oxygen, and in adhesiveness and retention performance after curing. Another object of the present invention is to provide a method for producing a laminate using the ultraviolet-curable pressure-sensitive adhesive composition. [Means for solving the problem]
[0009] Disclosure 1 relates to an ultraviolet-curable pressure-sensitive adhesive composition for use in printing, the ultraviolet-curable pressure-sensitive adhesive composition comprising a radical polymerizable monomer, a photopolymerization initiator, and a thickener, the radical polymerizable monomer comprising a compound having a cyclic structure containing a nitrogen atom, and having a viscosity of 3 Pa s or more and 100 Pa s or less as measured at 25°C and 10 rpm using an E-type viscometer. Disclosure 2 is a method for applying the above-mentioned ultraviolet-curable pressure-sensitive adhesive composition to a substrate, and then applying the composition to a substrate without sealing the coated surface at a wavelength of 365 nm and an illuminance of 500 mW / cm in an atmospheric environment. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 1 according to the present disclosure can be obtained by irradiating the ultraviolet-curable pressure-sensitive adhesive composition so as to obtain a cured product having a thickness of 50 μm with a reaction rate of 90% or more. The present disclosure 3 is the ultraviolet-curable pressure-sensitive adhesive composition according to the present disclosure 1 or 2, wherein the compound having a cyclic structure containing a nitrogen atom comprises at least one selected from the group consisting of radical polymerizable monomers having a lactam structure and maleimide derivatives. Disclosure 4 is an ultraviolet-curable pressure-sensitive adhesive composition according to Disclosure 3, wherein the compound having a cyclic structure containing a nitrogen atom comprises the maleimide derivative, and the maleimide derivative has at least a content of a maleimide derivative not having a structure in which hydrogen is bonded to a heteroatom of 50 mass% or more, or a content of a maleimide derivative having a structure in which hydrogen is bonded to a heteroatom of 10 parts by mass or less relative to 100 parts by mass of the radical polymerizable monomer, and the content of the maleimide derivative in 100 parts by mass of the radical polymerizable monomer is 0.1 part by mass or more and 20 parts by mass or less. The present disclosure 5 is the ultraviolet-curable pressure-sensitive adhesive composition of the present disclosure 3, wherein the compound having a cyclic structure containing a nitrogen atom comprises the radical polymerizable monomer having the lactam structure, and the content of the radical polymerizable monomer having the lactam structure in 100 parts by mass of the radical polymerizable monomer is 10 parts by mass or more and 60 parts by mass or less. Disclosure 6 is an ultraviolet-curable pressure-sensitive adhesive composition according to Disclosure 1, 2, 3, 4, or 5, wherein the radical polymerizable monomer contains 20 mass% or more of a monomer capable of serving as a hydrogen donor, the photopolymerization initiator contains at least one selected from the group consisting of hydrogen abstraction type photopolymerization initiators and polymer type photopolymerization initiators, the ultraviolet-curable pressure-sensitive adhesive composition further contains an amine compound, the amine compound contains an amine compound that does not have a structure in which hydrogen is bonded to a heteroatom in the amine compound in an amount of 50 mass% or more, and the content of the amine compound in a total of 100 mass parts of the ultraviolet-curable pressure-sensitive adhesive composition excluding the photopolymerization initiator is 0.1 part by mass or more and 10 parts by mass or less. The present disclosure 7 is the ultraviolet-curable pressure-sensitive adhesive composition according to the present disclosure 1, 2, 3, 4, 5, or 6, wherein the radical polymerizable monomer comprises a polyfunctional (meth)acrylic monomer. The present disclosure 8 is the ultraviolet-curable pressure-sensitive adhesive composition of the present disclosure 1, 2, 3, 4, 5, 6, or 7, wherein the thickener comprises at least one selected from the group consisting of a thermoplastic resin, a polymeric thixotropy regulator, and a solid thickener. The ninth disclosure is the ultraviolet-curable pressure-sensitive adhesive composition according to the eighth disclosure, wherein the thickener contains the thermoplastic resin, and the thermoplastic resin contains a (meth)acrylic copolymer. Disclosure 10 relates to a method for producing a pressure-sensitive adhesive composition, which is coated on a substrate, and then exposed to light at a wavelength of 365 nm and an illuminance of 500 mW / cm under atmospheric conditions without sealing the coated surface. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, or 9, wherein the glass transition temperature of a cured product having a thickness of 50 μm obtained by irradiating the ultraviolet-curable pressure-sensitive adhesive composition so as to satisfy the above conditions is −40° C. or higher and 20° C. or lower. The present disclosure 11 is a method for producing a pressure-sensitive adhesive composition by coating the above-mentioned ultraviolet-curable pressure-sensitive adhesive composition on a substrate, and then, without sealing the coated surface, performing a 365 nm wavelength, 500 mW / cm illuminance test under atmospheric conditions. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, wherein the gel fraction of a cured product having a thickness of 50 μm is 20 mass % or more and 80 mass % or less by irradiation. Disclosure 12 comprises a monofunctional radical polymerizable monomer, a photopolymerization initiator, and a crosslinking agent having two or more reactive functional groups in one molecule, the monofunctional radical polymerizable monomer comprises a compound having a cyclic structure containing a nitrogen atom, and the ultraviolet-curable pressure-sensitive adhesive composition is applied onto a substrate, and the applied surface is not sealed, and the ultraviolet-curable pressure-sensitive adhesive composition is cured under atmospheric conditions at a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 and a cured product having a thickness of 50 μm obtained by irradiating the cured product so as to have a reaction rate of 90% or more, a gel fraction of the cured product of from 20% to 80% by mass, and a temperature at or below 20° C., at which the loss tangent reaches a maximum value in a temperature range of 50° C. or less, in a viscoelasticity chart obtained by subjecting the cured product to dynamic viscoelasticity measurement using a shear method at measurement temperatures of −70° C. to 200° C. and a frequency of 1 Hz, is 20° C. or less. Disclosure 13 relates to an ultraviolet-curable pressure-sensitive adhesive composition according to Disclosure 12, wherein the compound having a cyclic structure containing a nitrogen atom includes at least one selected from the group consisting of monofunctional radically polymerizable monomers having a lactam structure and maleimide derivatives. Disclosure 14 is an ultraviolet-curable pressure-sensitive adhesive composition according to Disclosure 13, wherein the compound having a cyclic structure containing a nitrogen atom includes the maleimide derivative, and the maleimide derivative has at least a content of a maleimide derivative not having a structure in which hydrogen is bonded to a heteroatom of 50 mass% or more, or a content of a maleimide derivative having a structure in which hydrogen is bonded to a heteroatom of 10 parts by mass or less relative to 100 parts by mass of the monofunctional radical polymerizable monomer, and the content of the maleimide derivative in 100 parts by mass of the monofunctional radical polymerizable monomer is 0.1 part by mass or more and 20 parts by mass or less. Disclosure 15 is the ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 13, wherein the compound having a cyclic structure containing a nitrogen atom includes a monofunctional radical polymerizable monomer having the lactam structure, and the content of the monofunctional radical polymerizable monomer having the lactam structure in 100 parts by mass of the monofunctional radical polymerizable monomer is 10 parts by mass or more and 60 parts by mass or less. Disclosure 16 is an ultraviolet-curable pressure-sensitive adhesive composition according to Disclosure 12, 13, 14, or 15, wherein the monofunctional radically polymerizable monomer contains 20 mass% or more of a monomer capable of serving as a hydrogen donor, the photopolymerization initiator contains at least one selected from the group consisting of hydrogen abstraction type photopolymerization initiators and polymer type photopolymerization initiators, the ultraviolet-curable pressure-sensitive adhesive composition further contains an amine compound, the amine compound contains an amine compound that does not have a structure in which hydrogen is bonded to a heteroatom in the amine compound in an amount of 50 mass% or more, and the content of the amine compound in a total of 100 mass parts of the ultraviolet-curable pressure-sensitive adhesive composition excluding the photopolymerization initiator is 0.5 parts by mass or more and 8.0 parts by mass or less. Disclosure 17 is the ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 16, wherein the monomer capable of serving as the hydrogen donor is a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. The present disclosure 18 is an ultraviolet-curable pressure-sensitive adhesive composition according to the present disclosure 17, wherein the monofunctional radically polymerizable monomer contains 30 mass % or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. Disclosure 19 is the ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 12, 13, 14, 15, 16, 17, or 18, wherein the crosslinking agent has, as the reactive functional group, two or more of at least one selected from the group consisting of an isocyanate group, an epoxy group, an aldehyde group, a hydroxyl group, an amino group, a (meth)acryloyl group, and a vinyl group in one molecule. The present disclosure 20 is the ultraviolet-curable pressure-sensitive adhesive composition of the present disclosure 12, 13, 14, 15, 16, 17, 18, or 19, further comprising a thickener. Disclosure 21 is the ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 20, wherein the thickener is at least one selected from the group consisting of a thermoplastic resin, a polymeric thixotropy regulator, and a solid thickener. The present disclosure 22 is the ultraviolet-curable pressure-sensitive adhesive composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or 21, further comprising a tackifier. The present disclosure 23 is the ultraviolet-curable pressure-sensitive adhesive composition of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, or 22, further containing an antifoaming agent. Disclosure 24 is a method for producing a laminate in which the ultraviolet-curable pressure-sensitive adhesive composition of Disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, or 23 is applied onto a first adherend and exposed to light to form an adhesive layer, and a step of attaching a second adherend onto the adhesive layer, wherein the method for applying the ultraviolet-curable pressure-sensitive adhesive composition is screen printing, stencil printing, or reverse offset printing, and the ultraviolet-curable pressure-sensitive adhesive composition is applied entirely or partially onto the first adherend. The present disclosure 25 is a method for producing a laminate according to the present disclosure 24, wherein the first adherend and the second adherend are release-treated substrates. Disclosure 26 is a method for producing a laminate according to Disclosure 25, wherein the first adherend and the second adherend are base materials that have been subjected to a release treatment and an antistatic treatment. The present disclosure 27 is a method for producing a laminate according to the present disclosure 24, 25, or 26, in which the ultraviolet-curable pressure-sensitive adhesive composition is partially coated on the first adherend. The present invention will be described in detail below.
[0010] Hereinafter, the ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 1 will also be referred to as the "ultraviolet-curable pressure-sensitive adhesive composition of Invention 1," and the ultraviolet-curable pressure-sensitive adhesive composition of Disclosure 12 will also be referred to as the "ultraviolet-curable pressure-sensitive adhesive composition of Invention 2." Furthermore, matters common to the ultraviolet-curable pressure-sensitive adhesive composition of Invention 1 and the ultraviolet-curable pressure-sensitive adhesive composition of Invention 2 will be described as the "ultraviolet-curable pressure-sensitive adhesive composition of the present invention." The present inventors have investigated the preparation of an ultraviolet-curable adhesive composition containing a radical polymerizable monomer containing a compound having a cyclic structure containing a nitrogen atom, a photopolymerization initiator, and a thickener, and adjusting the viscosity at 25° C. to fall within a specific range. As a result, they have found that an ultraviolet-curable adhesive composition having excellent ultraviolet curability in the presence of oxygen, waterproofness and dustproofness, and shape stability after printing can be obtained, leading to the completion of Invention 1. By using the ultraviolet-curable adhesive composition of Invention 1, a square-shaped cured product that maintains its shape without gaps can be formed without generating waste by printing into a predetermined shape and irradiating with ultraviolet light in the atmosphere. The present inventors have also investigated how to make the reaction rate of a cured product obtained by UV curing an ultraviolet-curable pressure-sensitive adhesive composition containing a monofunctional radical polymerizable monomer containing a compound having a cyclic structure containing a nitrogen atom, a photopolymerization initiator, and a crosslinking agent under specific conditions to a specific value or more, a specific range of gel fraction, and a specific temperature or less. As a result, they have found that it is possible to obtain an ultraviolet-curable pressure-sensitive adhesive composition that is excellent in curability when irradiated with high-intensity ultraviolet light in the presence of oxygen, and in adhesiveness and retention performance after curing, and have completed the present invention 2.
[0011] The ultraviolet-curable pressure-sensitive adhesive composition of Invention 1 has a viscosity measured using an E-type viscometer at 25°C and 10 rpm of 3 Pa·s as a lower limit and 100 Pa·s as an upper limit. When the viscosity is within this range, the ultraviolet-curable pressure-sensitive adhesive composition of Invention 1 has excellent printability and shape stability after printing. The ultraviolet-curable pressure-sensitive adhesive composition of Invention 1 has a preferred lower limit of 5 Pa·s, more preferably 10 Pa·s, and a preferred upper limit of 70 Pa·s, more preferably 40 Pa·s, of the viscosity. The viscosity of the ultraviolet-curable pressure-sensitive adhesive composition of the first invention can be measured, for example, using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer with an appropriate cone plate under conditions of 25° C. and 10 rpm. The ultraviolet-curable pressure-sensitive adhesive composition of invention 2 has a viscosity at 25°C of preferably 5 mPa s at lower limit and 250,000 mPa s at upper limit. With the viscosity in this range, the ultraviolet-curable pressure-sensitive adhesive composition of invention 2 is suitable for printing. The ultraviolet-curable pressure-sensitive adhesive composition of invention 2 has a more preferable viscosity lower limit and 150,000 mPa s at upper limit. The viscosity of the ultraviolet-curable pressure-sensitive adhesive composition of invention 2 can be measured, for example, using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer with an appropriate cone plate under conditions of 25° C. and 10 rpm.
[0012] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 has a thixotropic index at 25° C. of preferably 1.05 at the lower limit and 2.5 at the upper limit. When the thixotropic index is in this range, the ultraviolet-curable pressure-sensitive adhesive composition has better printability and shape stability after printing. The more preferred lower limit of the thixotropic index is 1.1 and the more preferred upper limit is 2.0. In this specification, the "thixotropic index" refers to the value obtained by dividing the viscosity measured at 1 rpm using an E-type viscometer by the viscosity measured at 10 rpm.
[0013] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 contains a radically polymerizable monomer. By containing the radically polymerizable monomer, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 has excellent curability and adhesiveness after curing.
[0014] The radical polymerizable monomer includes a compound having a cyclic structure containing a nitrogen atom. By including the compound having a cyclic structure containing a nitrogen atom, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 has excellent ultraviolet curing properties in the presence of oxygen.
[0015] The compound having a cyclic structure containing a nitrogen atom preferably includes at least one selected from the group consisting of radically polymerizable monomers having a lactam structure and maleimide derivatives, and more preferably includes a maleimide derivative. The reaction system of the radical polymerizable monomer having the lactam structure and the maleimide derivative basically proceeds by a hydrogen abstraction (Type II) reaction. Photoradical polymerization by hydrogen abstraction reaction is not easily inhibited by oxygen, and can increase the surface curability. In addition, photoradical polymerization by hydrogen abstraction reaction does not produce a linear polymer as in cleavage (Type I) reaction, but produces a branched polymer, and the cohesive strength is also high. Therefore, by containing at least one selected from the group consisting of the radical polymerizable monomer having the lactam structure and the maleimide derivative, the ultraviolet-curable pressure-sensitive adhesive composition can obtain a cured product that is less susceptible to bleeding due to a decrease in surface curability and cohesive failure due to a decrease in surface curability and cohesive strength. In this specification, the above "maleimide derivative" means a compound having a maleimide group.
[0016] The maleimide derivative preferably has a content of at least 50 mass% of maleimide derivatives not having a structure in which hydrogen is bonded to a heteroatom, or a content of maleimide derivatives having a structure in which hydrogen is bonded to a heteroatom relative to 100 mass parts of the radical polymerizable monomer is 10 mass parts or less. This allows the cured product of the obtained ultraviolet-curable pressure-sensitive adhesive composition to have excellent impact resistance. More preferably, the content of maleimide derivatives having a structure in which hydrogen is bonded to a heteroatom relative to 100 mass parts of the radical polymerizable monomer is 5 mass parts or less. It is particularly preferable that the maleimide derivative contains only maleimide derivatives that do not have a structure in which hydrogen is bonded to a heteroatom.
[0017] Examples of the structure in which hydrogen is bonded to a hetero atom include a hydroxyl group, a carboxyl group, a primary amino group, and a secondary amino group.
[0018] Examples of the maleimide derivative not having a structure in which hydrogen is bonded to the heteroatom include N-cyclohexylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-octadecenylmaleimide, N-dodecenylmaleimide, etc. Among these, N-cyclohexylmaleimide is preferred.
[0019] Examples of the maleimide derivative having a structure in which hydrogen is bonded to the hetero atom include N-(4-carboxycyclohexylmethyl)maleimide, 4-hydroxyphenylmaleimide, and N-(4-anilinophenyl)maleimide.
[0020] In the ultraviolet-curable adhesive composition of the present invention 1, the content of the maleimide derivative in 100 parts by mass of the radical polymerizable monomer is preferably 0.1 parts by mass at the lower limit and 20 parts by mass at the upper limit. By making the content of the maleimide derivative within this range, the obtained ultraviolet-curable adhesive composition has better surface curability and adhesion. The more preferred lower limit of the content of the maleimide derivative is 0.5 parts by mass, and the more preferred upper limit is 10 parts by mass.
[0021] The radical polymerizable monomer having a lactam structure is preferably a compound represented by the following formula (1).
[0022] [ka]
[0023] In the formula (1), n represents an integer of 2 to 6.
[0024] Examples of the compound represented by the above formula (1) include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, etc. Among these, N-vinyl-ε-caprolactam is preferred.
[0025] In the ultraviolet-curable adhesive composition of the present invention 1, the content of the radical polymerizable monomer having the lactam structure in 100 parts by mass of the radical polymerizable monomer is preferably 10 parts by mass and 60 parts by mass. By the content of the radical polymerizable monomer having the lactam structure being within this range, the obtained ultraviolet-curable adhesive composition has better surface curing properties and adhesion. The more preferred lower limit of the content of the radical polymerizable monomer having the lactam structure is 15 parts by mass and the more preferred upper limit is 50 parts by mass.
[0026] The radical polymerizable monomer preferably contains a monomer capable of being a hydrogen donor. By containing the radical polymerizable monomer in combination with at least one selected from the group consisting of the radical polymerizable monomer having a lactam structure and a maleimide derivative, it is possible to obtain a cured product that is less susceptible to bleeding due to a decrease in surface curability and cohesive failure due to a decrease in curability and cohesive strength. In this specification, the above-mentioned "monomer capable of acting as a hydrogen donor" means a monomer having hydrogen capable of being used in a hydrogen abstraction reaction.
[0027] The monomer capable of serving as a hydrogen donor is preferably a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. The monomer capable of serving as a hydrogen donor is preferably a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond, so that the monomer can more easily provide hydrogen to a hydrogen abstraction reaction. In particular, the monomer capable of serving as a hydrogen donor is more preferably a monomer having at least one structure selected from the group consisting of an ether bond, a phenoxy group, and an amide bond.
[0028] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, the content of the monomer capable of being a hydrogen donor in the radical polymerizable monomer is preferably 20% by mass. When the content of the monomer capable of being a hydrogen donor in the radical polymerizable monomer is 20% by mass or more, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better surface curability. The more preferable lower limit of the content of the monomer capable of being a hydrogen donor in the radical polymerizable monomer is 35% by mass. From the viewpoint of impact resistance, the upper limit of the content of the monomer capable of serving as a hydrogen donor in the radical polymerizable monomer is preferably 90% by mass, and more preferably 70% by mass. In particular, the radical polymerizable monomer preferably contains 50% by mass or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. When the radical polymerizable monomer contains 50% by mass or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better curability and impact resistance of the cured product. More preferably, the radical polymerizable monomer contains 70% by mass or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.
[0029] The radical polymerizable monomer preferably contains a monofunctional (meth)acrylic monomer. When the radical polymerizable monomer contains the monofunctional (meth)acrylic monomer, the resulting ultraviolet-curable pressure-sensitive adhesive composition has superior adhesion. In this specification, the term "(meth)acrylic" means acrylic or methacrylic, the term "(meth)acrylic monomer" means a monomer having a (meth)acryloyl group, and the term "(meth)acryloyl" means acryloyl or methacryloyl. In addition, in this specification, the term "monofunctional (meth)acrylic monomer" means a monomer having one (meth)acryloyl group in one molecule.
[0030] Examples of the monofunctional (meth)acrylic monomer include a monofunctional (meth)acrylic acid ester compound and a monofunctional (meth)acrylamide compound.
[0031] Examples of the monofunctional (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. , cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tetrahydrofurfuryl alcohol acrylic acid polymer ester, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-Octafluoropentyl (meth)acrylate, Imido (meth)acrylate, Dimethylaminoethyl (meth)acrylate, Diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 2-(((butylamino)carbonyl)oxy)ethyl (meth)acrylate, (3-propyloxetan-3-yl)methyl (meth)acrylate, (3-butyloxetan-3-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)ethyl (meth)acrylate , (3-ethyloxetan-3-yl)propyl (meth)acrylate, (3-ethyloxetan-3-yl)butyl (meth)acrylate, (3-ethyloxetan-3-yl)pentyl (meth)acrylate, (3-ethyloxetan-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-isobutyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-cyclohexyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, and cyclic trimethylolpropane formal acrylate. In this specification, the term "(meth)acrylate" means acrylate or methacrylate.
[0032] Examples of the monofunctional (meth)acrylamide compound include N,N-dimethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide.
[0033] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, the content of the monofunctional (meth)acrylic monomer in 100 parts by mass of the radical polymerizable monomer is preferably 10 parts by mass at the lower limit and 99 parts by mass at the upper limit. When the content of the monofunctional (meth)acrylic monomer is within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better printability and adhesion to various substrates. The more preferred lower limit of the content of the monofunctional (meth)acrylic monomer is 20 parts by mass, and the more preferred upper limit is 95 parts by mass.
[0034] The radical polymerizable monomer preferably contains a polyfunctional (meth)acrylic monomer. By containing the polyfunctional (meth)acrylic monomer, the ultraviolet-curable pressure-sensitive adhesive composition of invention 1 has better adhesiveness and retention performance after curing. In this specification, the above-mentioned "polyfunctional (meth)acrylic monomer" means a monomer having two or more (meth)acryloyl groups in one molecule.
[0035] Examples of the polyfunctional (meth)acrylic monomer include polyfunctional urethane (meth)acrylates, polyfunctional (meth)acrylic acid ester compounds, and polyfunctional epoxy (meth)acrylates. In this specification, the term "(meth)acrylate" means acrylate or methacrylate, and the term "epoxy (meth)acrylate" refers to a compound in which all epoxy groups in an epoxy compound have been reacted with (meth)acrylic acid.
[0036] The polyfunctional urethane (meth)acrylate can be obtained, for example, by reacting an isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.
[0037] Examples of the isocyanate compound that is a raw material for the polyfunctional urethane (meth)acrylate include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.
[0038] As the isocyanate compound serving as a raw material for the polyfunctional urethane (meth)acrylate, a chain-extended isocyanate compound obtained by reacting a polyol with an excess of an isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0039] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, and mono(meth)acrylates or di(meth)acrylates of trihydric alcohols. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin.
[0040] Examples of the polyfunctional (meth)acrylic acid ester compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-Propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, tri Examples of the cyclodecane dimethanol di(meth)acrylate include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0041] Examples of the polyfunctional epoxy(meth)acrylate include bisphenol A type epoxy(meth)acrylate, bisphenol F type epoxy(meth)acrylate, bisphenol E type epoxy(meth)acrylate, and caprolactone modified versions of these.
[0042] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, the content of the polyfunctional (meth)acrylic monomer in 100 parts by mass of the radical polymerizable monomer is preferably 0.5 parts by mass at the lower limit and 20 parts by mass at the upper limit. When the content of the polyfunctional (meth)acrylic monomer is within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better adhesion and retention performance after curing. The more preferred lower limit of the content of the polyfunctional (meth)acrylic monomer is 1 part by mass, and the more preferred upper limit is 10 parts by mass.
[0043] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 contains a monofunctional radically polymerizable monomer. By containing the monofunctional radically polymerizable monomer, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 has excellent adhesiveness after curing. In this specification, the above-mentioned "monofunctional radically polymerizable monomer" means a monomer having one radically polymerizable group in one molecule.
[0044] The monofunctional radical polymerizable monomer includes a compound having a cyclic structure containing a nitrogen atom. By including the compound having a cyclic structure containing a nitrogen atom, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 has excellent ultraviolet curing properties in the presence of oxygen.
[0045] The compound having a cyclic structure containing a nitrogen atom preferably contains at least one selected from the group consisting of monofunctional radically polymerizable monomers having a lactam structure and maleimide derivatives, and more preferably contains a maleimide derivative. The reaction system of the monofunctional radical polymerizable monomer having a lactam structure and the maleimide derivative basically proceeds by a hydrogen abstraction (Type II) reaction. Photoradical polymerization by hydrogen abstraction reaction is not easily inhibited by oxygen, and can increase the surface curability. In addition, photoradical polymerization by hydrogen abstraction reaction does not produce a linear polymer as in cleavage (Type I) reaction, but produces a branched polymer, and the cohesive strength is also high. Therefore, by containing at least one selected from the group consisting of the monofunctional radical polymerizable monomer having a lactam structure and the maleimide derivative, the ultraviolet-curable pressure-sensitive adhesive composition can obtain a cured product that is less susceptible to bleeding due to a decrease in surface curability and cohesive failure due to a decrease in surface curability and cohesive strength.
[0046] In the ultraviolet-curable adhesive composition of the present invention 2, the maleimide derivative preferably has a content of at least 50 mass% of maleimide derivatives not having a structure in which hydrogen is bonded to a heteroatom, or a content of maleimide derivatives having a structure in which hydrogen is bonded to a heteroatom relative to 100 mass parts of the monofunctional radical polymerizable monomer is 10 mass parts or less. This allows the cured product of the obtained ultraviolet-curable adhesive composition to have excellent adhesive strength and holding power. More preferably, the content of maleimide derivatives having a structure in which hydrogen is bonded to a heteroatom relative to 100 mass parts of the monofunctional radical polymerizable monomer is 5 mass parts or less. It is particularly preferable that the maleimide derivative contains only maleimide derivatives that do not have a structure in which hydrogen is bonded to a heteroatom.
[0047] Examples of the structure in which hydrogen is bonded to a hetero atom include a hydroxyl group, a carboxyl group, a primary amino group, and a secondary amino group.
[0048] Examples of the maleimide derivative not having a structure in which hydrogen is bonded to the heteroatom include N-cyclohexylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-octadecenylmaleimide, N-dodecenylmaleimide, etc. Among these, N-cyclohexylmaleimide is preferred.
[0049] Examples of the maleimide derivative having a structure in which hydrogen is bonded to the hetero atom include N-(4-carboxycyclohexylmethyl)maleimide, 4-hydroxyphenylmaleimide, and N-(4-anilinophenyl)maleimide.
[0050] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the content of the maleimide derivative in 100 parts by mass of the monofunctional radical polymerizable monomer is preferably 0.1 parts by mass at the lower limit and 20 parts by mass at the upper limit. When the content of the maleimide derivative is within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better surface curability and adhesion. The more preferred lower limit of the content of the maleimide derivative is 0.5 parts by mass at the lower limit and 10 parts by mass at the upper limit.
[0051] The monofunctional radically polymerizable monomer having a lactam structure is preferably a compound represented by the following formula (1).
[0052] [ka]
[0053] In the formula (1), n represents an integer of 2 to 6.
[0054] Examples of the compound represented by the above formula (1) include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, etc. Among these, N-vinyl-ε-caprolactam is preferred.
[0055] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the content of the monofunctional radical polymerizable monomer having the lactam structure in 100 parts by mass of the monofunctional radical polymerizable monomer is preferably 10 parts by mass, and the preferred upper limit is 60 parts by mass. By the content of the monofunctional radical polymerizable monomer having the lactam structure being within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better surface curing properties and adhesion. The more preferred lower limit of the content of the monofunctional radical polymerizable monomer having the lactam structure is 15 parts by mass, and the more preferred upper limit is 50 parts by mass.
[0056] The monofunctional radical polymerizable monomer preferably contains a monomer capable of being a hydrogen donor. By containing the monofunctional radical polymerizable monomer in combination with at least one selected from the group consisting of the monofunctional radical polymerizable monomer having a lactam structure and a maleimide derivative, it is possible to obtain a cured product that is less susceptible to bleeding due to a decrease in surface curability and cohesive failure due to a decrease in curability and cohesive strength.
[0057] The monomer capable of serving as a hydrogen donor is preferably a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. The monomer capable of serving as a hydrogen donor is preferably a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond, so that the monomer can more easily provide hydrogen to a hydrogen abstraction reaction. In particular, the monomer capable of serving as a hydrogen donor is more preferably a monomer having at least one structure selected from the group consisting of an ether bond, a phenoxy group, and an amide bond.
[0058] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the preferred lower limit of the content of the monomer capable of being a hydrogen donor in the monofunctional radical polymerizable monomer is 20% by mass. When the content of the monomer capable of being a hydrogen donor in the monofunctional radical polymerizable monomer is 20% by mass or more, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better surface curability. The more preferred lower limit of the content of the monomer capable of being a hydrogen donor in the monofunctional radical polymerizable monomer is 35% by mass. From the viewpoint of adhesion and retention performance, the upper limit of the content of the monomer capable of serving as a hydrogen donor in the monofunctional radically polymerizable monomer is preferably 90% by mass, and more preferably 70% by mass. In particular, the monofunctional radical polymerizable monomer preferably contains 30% by mass or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. When the monofunctional radical polymerizable monomer contains 30% by mass or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better curability and better adhesion and retention of the cured product. The monofunctional radical polymerizable monomer more preferably contains 50% by mass or more, and even more preferably contains 70% by mass or more, of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.
[0059] The monofunctional radical polymerizable monomer preferably contains a monofunctional (meth)acrylic monomer. When the monofunctional radical polymerizable monomer contains the monofunctional (meth)acrylic monomer, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better adhesion.
[0060] Examples of the monofunctional (meth)acrylic monomer include a monofunctional (meth)acrylic acid ester compound and a monofunctional (meth)acrylamide compound.
[0061] Examples of the monofunctional (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. , cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, tetrahydrofurfuryl alcohol acrylic acid polymer ester, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-Octafluoropentyl (meth)acrylate, Imido (meth)acrylate, Dimethylaminoethyl (meth)acrylate, Diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, (3-ethyloxetan-3-yl)methyl (meth)acrylate, 2-(((butylamino)carbonyl)oxy)ethyl (meth)acrylate, (3-propyloxetan-3-yl)methyl (meth)acrylate, (3-butyloxetan-3-yl)methyl (meth)acrylate, (3-ethyloxetan-3-yl)ethyl (meth)acrylate , (3-ethyloxetan-3-yl)propyl (meth)acrylate, (3-ethyloxetan-3-yl)butyl (meth)acrylate, (3-ethyloxetan-3-yl)pentyl (meth)acrylate, (3-ethyloxetan-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-isobutyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-cyclohexyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, and cyclic trimethylolpropane formal acrylate.
[0062] Examples of the monofunctional (meth)acrylamide compound include N,N-dimethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide.
[0063] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention contains a photopolymerization initiator. The photopolymerization initiator preferably includes at least one selected from the group consisting of hydrogen abstraction type photopolymerization initiators and polymer type photopolymerization initiators. By using at least one selected from the group consisting of hydrogen abstraction type photopolymerization initiators and polymer type photopolymerization initiators as the photopolymerization initiator, it becomes possible to obtain a cured product in which bleeding due to a decrease in surface curability and cohesive failure due to a decrease in surface curability and cohesive strength are less likely to occur in the obtained ultraviolet-curable pressure-sensitive adhesive composition.
[0064] The hydrogen abstraction type photopolymerization initiator is preferably a benzophenone-based photopolymerization initiator.The benzophenone-based photopolymerization initiator can be exemplified by benzophenone, 4-chlorobenzophenone, 4,4'-dimethylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, o-benzoyl methyl benzoate, 3,3'-dimethyl-4-methoxybenzophenone, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 4-morpholinobenzophenone, 4,4'-diphenoxybenzophenone, 4-hydroxybenzophenone, 2-carboxybenzophenone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methyl-propionyl)-benzyl)-phenyl)-2-methyl-propan-1-one, 1-(4-(4-benzoylphenylthio)phenyl)-2-tosyl-2-methyl-1-propanone, 3-ketocoumarin, etc.
[0065] Among the above hydrogen abstraction type photopolymerization initiators, commercially available ones include, for example, Esacure TZT and Omnirad 4MBZ (both manufactured by IGM Resins).
[0066] Examples of the polymer type photopolymerization initiator include a polymer of ethyl (2,4,6-trimethylbenzoyl)-phenyl phosphonate, polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butanoylphenyl)piperazine)propionate, and bis(benzophenone-2-carboxylic acid) polyethylene glycol ester.
[0067] Among the above polymer type photopolymerization initiators, commercially available ones include, for example, Omnipol TP, Omnipol 910, Omnipol 2702 (all manufactured by IGM Resins), and the like.
[0068] As the photopolymerization initiator, a cleavage type photopolymerization initiator can also be used. Examples of the cleavage type photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0069] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, the content of the photopolymerization initiator is preferably 0.5 parts by mass at the lower limit and 15 parts by mass at the upper limit with respect to 100 parts by mass of the radical polymerizable monomer. By having the content of the photopolymerization initiator within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition is more excellent in storage stability, curability, and adhesiveness after curing. The more preferred lower limit of the content of the photopolymerization initiator is 3 parts by mass, and the more preferred upper limit is 9 parts by mass. In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the content of the photopolymerization initiator is preferably 0.5 parts by mass at the lower limit and 15 parts by mass at the upper limit relative to 100 parts by mass of the monofunctional radical polymerizable monomer. By setting the content of the photopolymerization initiator within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition is more excellent in storage stability, curability, and adhesiveness after curing. The more preferred lower limit of the content of the photopolymerization initiator is 1 part by mass, and the more preferred upper limit is 9 parts by mass.
[0070] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention preferably contains an amine compound. As described above, by using the amine compound in combination with the hydrogen abstraction type photopolymerization initiator, it becomes possible to obtain an ultraviolet-curable pressure-sensitive adhesive composition that is less susceptible to bleeding due to a decrease in surface curability and cohesive failure due to a decrease in surface curability and cohesive strength, and thus a cured product that is less susceptible to bleeding due to a decrease in surface curability and cohesive strength.
[0071] The amine compound preferably has a content of 50% by mass or more of amine compounds that do not have a structure in which hydrogen is bonded to a heteroatom. By using an amine compound having a content of 50% by mass or more of amine compounds that do not have a structure in which hydrogen is bonded to a heteroatom, the obtained ultraviolet-curable pressure-sensitive adhesive composition can obtain a cured product that is less likely to cause bleeding due to a decrease in surface curability and cohesive failure due to a decrease in surface curability and cohesive strength. The amine compound more preferably has a content of 75% by mass or more of amine compounds that do not have a structure in which hydrogen is bonded to a heteroatom, and most preferably has a content of 100% by mass.
[0072] Examples of the amine compound not having a structure in which hydrogen is bonded to a heteroatom include (bis-N,N-(4-dimethylaminobenzoyl)oxyethylene-1-yl)-methylamine, bis(2-morpholinoethyl)ether, 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidinyl)decanedioate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, and bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacic acid.
[0073] Commercially available amine compounds that do not have a structure in which hydrogen is bonded to a heteroatom include, for example, Esacure A198 (manufactured by IGM Resins), U-cat 660 (manufactured by San-Apro), Eversorb 93 (manufactured by Everlight Chemical), Adeka STAB LA-52, and Adeka STAB LA-72 (all manufactured by ADEKA Corporation).
[0074] In the ultraviolet-curable adhesive composition of the present invention 1, the content of the amine compound in the total of 100 parts by mass of the ultraviolet-curable adhesive composition excluding the photopolymerization initiator is preferably 0.1 parts by mass at the lower limit and 10 parts by mass at the upper limit. When the content of the amine compound is 0.1 parts by mass or more, the obtained ultraviolet-curable adhesive composition has better surface curing properties. When the content of the amine compound is 10 parts by mass or less, the obtained adhesive sheet is less likely to cause cohesive failure. The more preferable lower limit of the content of the amine compound is 0.5 parts by mass, and the more preferable upper limit is 8.0 parts by mass. In the ultraviolet-curable adhesive composition of the present invention 2, the content of the amine compound in the total of 100 parts by mass of the ultraviolet-curable adhesive composition excluding the photopolymerization initiator is preferably 0.5 parts by mass at the lower limit and 8.0 parts by mass at the upper limit. When the content of the amine compound is 0.5 parts by mass or more, the obtained ultraviolet-curable adhesive composition has better surface curing properties. When the content of the amine compound is 8.0 parts by mass or less, the obtained adhesive sheet is less likely to cause cohesive failure. The more preferable lower limit of the content of the amine compound is 1.0 parts by mass, and the more preferable upper limit is 5.0 parts by mass.
[0075] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 contains a thickener. By containing the thickener, it becomes easy to adjust the viscosity and thixotropic index of the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 to the above-mentioned ranges. In addition, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 may further contain a thickener.
[0076] The thickener preferably contains at least one selected from the group consisting of a thermoplastic resin, a polymer-type thixotropy regulator, and a solid thickener.
[0077] The thermoplastic resin is preferably a compound that does not contain a reactive double bond, or a compound that has a reactive double bond but does not substantially exhibit photoradical polymerization reactivity.
[0078] Examples of the thermoplastic resin include (meth)acrylic copolymers, polyolefins, polyesters, polyamides, polyurethanes, etc. Among these, it is preferable that the thermoplastic resin contains a (meth)acrylic copolymer.
[0079] The (meth)acrylic copolymer may, for example, be a solvent-free acrylic polymer. Examples of the solvent-free acrylic polymer include a polymer of at least one monomer selected from (meth)acrylic acid alkyl esters having an alkyl group with 1 to 20 carbon atoms, and a copolymer of the monomer and another copolymerizable monomer. Among the above-mentioned solvent-free acrylic polymers, commercially available ones include, for example, the ARUFON-UP1000 series, UH2000 series, UC3000 series (all manufactured by Toagosei Co., Ltd.), the Clarity LA series, and the Clarity LK series (all manufactured by Kuraray Co., Ltd.).
[0080] The preferred lower limit of the weight average molecular weight of the thermoplastic resin is 5000, and the preferred upper limit is 800,000. By setting the weight average molecular weight of the thermoplastic resin within this range, it becomes easier to adjust the viscosity and thixotropic index of the obtained ultraviolet-curable pressure-sensitive adhesive composition to the above-mentioned range. The more preferred lower limit of the weight average molecular weight of the thermoplastic resin is 10,000, and the more preferred upper limit is 500,000. In this specification, the weight average molecular weight is a value obtained by measuring using tetrahydrofuran as a solvent by gel permeation chromatography (GPC) and converting the weight average molecular weight into polystyrene equivalent. Examples of columns used for measuring the weight average molecular weight converted into polystyrene equivalent by GPC include Shodex LF-804 (manufactured by Showa Denko KK).
[0081] In the ultraviolet-curable adhesive composition of the present invention 1, when the thermoplastic resin is contained as the thickener, the content of the thermoplastic resin is preferably 5 parts by mass at the lower limit and 85 parts by mass at the upper limit with respect to 100 parts by mass of the radical polymerizable monomer. By the content of the thermoplastic resin being within this range, it becomes easier to adjust the viscosity and thixotropic index of the obtained ultraviolet-curable adhesive composition to the above-mentioned range, and the decrease in adhesion at high temperatures can also be suppressed. The more preferred lower limit of the content of the thermoplastic resin is 15 parts by mass, and the more preferred upper limit is 65 parts by mass. In addition, in the ultraviolet-curable adhesive composition of the present invention 2, when the thermoplastic resin is contained as the thickener, the content of the thermoplastic resin is preferably 1.0 parts by mass and 70 parts by mass relative to 100 parts by mass of the monofunctional radical polymerizable monomer. By the content of the thermoplastic resin being within this range, the viscosity of the obtained ultraviolet-curable adhesive composition is improved, a thick coating film can be formed, the printability is improved, and the decrease in adhesion at high temperatures can be suppressed. The more preferable lower limit of the content of the thermoplastic resin is 5.0 parts by mass, and the more preferable upper limit is 60 parts by mass.
[0082] Examples of the polymeric thixotropy adjusting agent include amide, castor oil, polyether phosphate ester, and the like.
[0083] The solid thickener may be inorganic particles or organic particles. Examples of the inorganic particles include insulating and heat-dissipating fillers, conductive fillers, and high dielectric constant fillers. Examples of the insulating and heat-dissipating filler include talc, silica, alumina, aluminum nitride, magnesium oxide, and diamond. Examples of the conductive filler include carbon filler, metal filler, metal oxide filler, and metal-coated filler. An example of the high dielectric constant filler is barium titanate. Examples of the organic particles include (meth)acrylic copolymer particles, melamine resin particles, (meth)acrylic-styrene copolymer particles, and organic-inorganic composite particles. The organic-inorganic composite particles include, for example, particles made of silicone-acrylic resin. The organic particles may be hollow particles or thermally expanded particles.
[0084] The solid thickener has a preferred lower limit of 5 nm and a preferred upper limit of 20 μm. The solid thickener has a preferred average particle size within this range, so that the resulting ultraviolet-curable adhesive composition has better printability. The solid thickener has a more preferred lower limit of 10 nm and a more preferred upper limit of 10 μm. The average particle size of the solid thickener can be measured by dispersing the solid thickener in a solvent (water, organic solvent, etc.) using a particle size distribution measuring device such as NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0085] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, when the solid thickener is contained as the thickener, the content of the solid thickener is preferably 1.0 parts by mass at the lower limit and 70 parts by mass at the upper limit relative to 100 parts by mass of the radical polymerizable monomer. When the content of the solid thickener in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is within this range, it becomes easier to adjust the viscosity and thixotropic index of the obtained ultraviolet-curable pressure-sensitive adhesive composition to the above-mentioned ranges. The more preferred lower limit of the content of the solid thickener in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is 2.0 parts by mass, and the more preferred upper limit is 50 parts by mass. In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, when the solid thickener is contained as the thickener, the content of the solid thickener is preferably 1.0 parts by mass at the lower limit and 70 parts by mass at the upper limit relative to 100 parts by mass of the monofunctional radical polymerizable monomer. When the content of the solid thickener in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 is within this range, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better printability. The more preferred lower limit of the content of the solid thickener in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 is 2.0 parts by mass, and the more preferred upper limit is 50 parts by mass.
[0086] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 contains a crosslinking agent having two or more reactive functional groups in one molecule. The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 preferably contains a crosslinking agent having two or more reactive functional groups in one molecule. By containing the crosslinking agent, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention can easily adjust the gel fraction of the cured product to the range described below, and has excellent adhesion and retention performance after curing.
[0087] In the ultraviolet-curable pressure-sensitive adhesive composition of the second invention, the crosslinking agent preferably has, as the reactive functional group, at least one selected from the group consisting of an isocyanate group, an epoxy group, an aldehyde group, a hydroxyl group, an amino group, a (meth)acryloyl group, and a vinyl group, in one molecule, two or more of which are selected from the group consisting of an isocyanate group, an epoxy group, and a (meth)acryloyl group, and more preferably has, in one molecule, two or more of which are at least one selected from the group consisting of an isocyanate group, an epoxy group, and a (meth)acryloyl group. In the ultraviolet-curable pressure-sensitive adhesive composition of the first invention, the crosslinking agent preferably has, as the reactive functional group, at least one type selected from the group consisting of an isocyanate group, an epoxy group, an aldehyde group, a hydroxyl group, and an amino group, in one molecule, two or more of which are selected from the group consisting of an isocyanate group and an epoxy group, in one molecule, more preferably has at least one type selected from the group consisting of an isocyanate group and an epoxy group, in one molecule.
[0088] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, examples of the crosslinking agent having two or more (meth)acryloyl groups in one molecule include polyfunctional urethane (meth)acrylates, polyfunctional (meth)acrylic acid ester compounds, and polyfunctional epoxy (meth)acrylates.
[0089] The polyfunctional urethane (meth)acrylate can be obtained, for example, by reacting an isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.
[0090] Examples of the isocyanate compound that is a raw material for the polyfunctional urethane (meth)acrylate include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.
[0091] As the isocyanate compound serving as a raw material for the polyfunctional urethane (meth)acrylate, a chain-extended isocyanate compound obtained by reacting a polyol with an excess of an isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0092] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, and mono(meth)acrylates or di(meth)acrylates of trihydric alcohols. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin.
[0093] Examples of the polyfunctional (meth)acrylic acid ester compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-Propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadiene Di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl(meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylol dimethacrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate , pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0094] Examples of the polyfunctional epoxy(meth)acrylate include bisphenol A type epoxy(meth)acrylate, bisphenol F type epoxy(meth)acrylate, bisphenol E type epoxy(meth)acrylate, and caprolactone modified versions of these.
[0095] Examples of the crosslinking agent having an isocyanate group include polyisocyanate, polymeric MDI, and blocked isocyanate.
[0096] An example of the crosslinking agent having an epoxy group is N,N,N',N'-tetraglycidyl-m-xylylenediamine.
[0097] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the content of the crosslinking agent relative to 100 parts by mass of the monofunctional radical polymerizable monomer is preferably 0.5 parts by mass. When the content of the crosslinking agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 is 0.5 parts by mass or more, the obtained ultraviolet-curable pressure-sensitive adhesive composition has better retention performance after curing. The more preferable lower limit of the content of the crosslinking agent is 1.0 parts by mass. From the viewpoint of adhesive strength, the upper limit of the content of the crosslinking agent in the ultraviolet-curable pressure-sensitive adhesive composition of invention 2 is preferably 10 parts by mass, and more preferably 5.0 parts by mass. In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, the preferred lower limit of the content of the crosslinking agent relative to 100 parts by mass of the radical polymerizable monomer is 0.5 parts by mass. When the content of the crosslinking agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is 0.5 parts by mass or more, the resulting ultraviolet-curable pressure-sensitive adhesive composition becomes more excellent in adhesion and retention performance after curing. The more preferred lower limit of the content of the crosslinking agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is 1.0 part by mass. From the viewpoints of printability and impact resistance of the cured product, the upper limit of the content of the crosslinking agent in the ultraviolet-curable pressure-sensitive adhesive composition of invention 1 is preferably 10 parts by mass, and more preferably 5.0 parts by mass.
[0098] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention may further contain a tackifier. Examples of the tackifier include rosin-based resins and terpene-based resins.
[0099] The rosin-based resin may, for example, be rosin diol. The rosin diol is not particularly limited as long as it is a rosin-modified diol having two rosin skeletons and two hydroxyl groups in the molecule. Diols having a rosin component in the molecule are called rosin polyols, and these include polyether types such as polypropylene glycol (PPG) in which the skeleton excluding the rosin component is polyether, and polyester types such as condensation polyester polyols, lactone polyester polyols, and polycarbonate diols. Examples of the rosin diol include rosin ester obtained by reacting rosin with a polyhydric alcohol, epoxy-modified rosin ester obtained by reacting rosin with an epoxy compound, and modified rosin having a hydroxyl group, such as polyether having a rosin skeleton, etc. These can be produced by conventionally known methods.
[0100] Examples of the rosin component include abietic acid and pimaric acid type resin acids such as dehydroabietic acid, dihydroabietic acid, tetrahydroabietic acid, diabietic acid, neoabietic acid, and levopimaric acid, which are derivatives of abietic acid, hydrogenated rosins obtained by hydrogenating these acids, and disproportionated rosins obtained by disproportionating these acids.
[0101] Among the above rosin-based resins, commercially available ones include, for example, Pine Crystal D-6011, Pine Crystal KE-615-3, Pine Crystal KR-614, Pine Crystal KE-100, Pine Crystal KE-311, Pine Crystal KE-359, Pine Crystal KE-604, Pine Crystal D-6250 (all manufactured by Arakawa Chemical Industries Co., Ltd.), and the like.
[0102] Examples of the terpene resin include terpene phenol resins. The terpene phenol resin is a copolymer of phenol and a terpene resin, which is an essential oil component obtained from natural products such as rosin and orange peel, and also includes partially hydrogenated terpene phenol resins in which at least a portion of the copolymer is hydrogenated, or fully hydrogenated terpene phenol resins in which the copolymer is completely hydrogenated. Here, the fully hydrogenated terpene phenolic resin is a terpene resin obtained by substantially completely hydrogenating a terpene phenolic resin, and the partially hydrogenated terpene phenolic resin is a terpene resin obtained by partially hydrogenating a terpene phenolic resin. The terpene phenolic resin has a double bond derived from a terpene and an aromatic ring double bond derived from a phenol. Therefore, the fully hydrogenated terpene phenolic resin means a resin in which both the terpene portion and the phenol portion are completely or almost hydrogenated, and the partially hydrogenated terpene phenolic resin means a resin in which the degree of hydrogenation of these portions is not complete but partial. The hydrogenation method and reaction form are not particularly limited. Among the above terpene phenol-based resins, examples of commercially available ones include YS Polystar NH (fully hydrogenated terpene phenol-based resin) manufactured by Yasuhara Chemical Co., Ltd.
[0103] The content of the tackifier is preferably 5 parts by mass at the lower limit and 50 parts by mass at the upper limit with respect to 100 parts by mass of the total of the ultraviolet-curable adhesive composition not including the tackifier. By the content of the tackifier being within this range, the obtained ultraviolet-curable adhesive composition has better adhesion to various substrates. The more preferred lower limit of the content of the tackifier is 10 parts by mass, and the more preferred upper limit is 35 parts by mass.
[0104] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention may contain a defoaming agent. Examples of the defoaming agent include silicone-based defoaming agents, acrylic polymer-based defoaming agents, vinyl ether polymer-based defoaming agents, and olefin polymer-based defoaming agents.
[0105] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1, the preferred lower limit of the content of the defoaming agent relative to 100 parts by mass of the radical polymerizable monomer is 0.1 parts by mass, and the preferred upper limit is 5 parts by mass. When the content of the defoaming agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is within this range, the resulting ultraviolet-curable pressure-sensitive adhesive composition has better printability. The more preferred lower limit of the content of the defoaming agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is 0.5 parts by mass, and the more preferred upper limit is 3 parts by mass. In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the preferred lower limit of the content of the defoaming agent relative to 100 parts by mass of the monofunctional radical polymerizable monomer is 0.1 parts by mass, and the preferred upper limit is 5 parts by mass. When the content of the defoaming agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 is within this range, the resulting ultraviolet-curable pressure-sensitive adhesive composition has better printability. The more preferred lower limit of the content of the defoaming agent in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 is 0.5 parts by mass, and the more preferred upper limit is 3 parts by mass.
[0106] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention may contain a plasticizer. Examples of the plasticizer include organic acid esters, organic phosphates, and organic phosphites.
[0107] Examples of the organic acid ester include monobasic organic acid esters and polybasic organic acid esters. Examples of the monobasic organic acid ester include glycol esters obtained by reacting a monobasic organic acid such as butyric acid, isobutyric acid, caproic acid, 2-ethylbutyric acid, heptyl acid, n-octylic acid, 2-ethylhexyl acid, pelargonic acid (n-nonylic acid), or decylic acid with a glycol such as triethylene glycol, tetraethylene glycol, or tripropylene glycol. Examples of the polybasic organic acid ester include ester compounds obtained by reacting a polybasic organic acid such as adipic acid, sebacic acid, or azelaic acid with an alcohol having a linear or branched structure having 4 to 8 carbon atoms.
[0108] Specific examples of the organic acid ester include triethylene glycol-di-2-ethylbutyrate (3GH), triethylene glycol-di-2-ethylhexanoate (3GO), triethylene glycol dicaprylate, triethylene glycol di-n-octanoate, and triethylene glycol di-n-heptanoate (3G7). In addition, tetraethylene glycol-di-n-heptanoate (4G7), tetraethylene glycol-di-2-ethylhexanoate, dibutyl sebacate, dioctyl azelate, dibutyl carbitol adipate, ethylene glycol di-2-ethylbutyrate, and 1,3-propylene glycol di-2-ethylbutyrate. In addition, 1,4-butylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, and dipropylene glycol di-2-ethylbutyrate are also included. Other examples include triethylene glycol di-2-ethylpentanoate, tetraethylene glycol di-2-ethylbutyrate (4GH), diethylene glycol dicapryate, dihexyl adipate (DHA), dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, etc. Other examples include oil-modified sebacic acid alkyd, a mixture of a phosphate ester and an adipate ester, and a mixed adipate ester made from an alkyl alcohol having 4 to 9 carbon atoms and a cyclic alcohol having 4 to 9 carbon atoms.
[0109] The organic phosphate or organic phosphite may be a compound obtained by a condensation reaction between phosphoric acid or phosphorous acid and an alcohol. Among them, a compound obtained by a condensation reaction between an alcohol having 1 to 12 carbon atoms and phosphoric acid or phosphorous acid is preferable. Examples of the alcohol having 1 to 12 carbon atoms include methanol, ethanol, butanol, hexanol, 2-ethylbutanol, heptanol, octanol, 2-ethylhexanol, decanol, dodecanol, butoxyethanol, butoxyethoxyethanol, and benzyl alcohol. Examples of the organic phosphate ester or organic phosphite ester include trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tri(2-ethylhexyl) phosphate, tri(butoxyethyl) phosphate, tri(2-ethylhexyl) phosphite, isodecylphenyl phosphate, and triisopropyl phosphate.
[0110] The ultraviolet-curable pressure-sensitive adhesive composition of the present invention may further contain various known additives, such as a silane coupling agent, a sensitizer, a heat curing agent, a cure retarder, an antioxidant, a storage stabilizer, a dispersant, an ultraviolet absorber, a radical polymerization inhibitor, a light stabilizer, a heat stabilizer, a dehydrating agent, a colorant, an antibacterial / antifungal agent, a flame retardant, a leveling agent, a wetting / dispersing agent, an anti-settling agent, an anti-sagging agent, an emulsifier, an anti-fogging agent, a lubricant, an antifouling agent, an antistatic agent, and a conductive agent, within the scope of not impairing the object of the present invention. In addition, from the viewpoint of preventing a decrease in UV reactivity, it is preferable that the UV-curable pressure-sensitive adhesive composition of the present invention is substantially free of organic solvents. Specifically, it is preferable that the content of the organic solvent is 1.5 mass% or less relative to 100 mass% of the UV-curable pressure-sensitive adhesive composition.
[0111] The method for preparing the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 can be, for example, a method in which the radical polymerizable monomer, the photopolymerization initiator, the thickener, the amine compound, and additives added as necessary are mixed using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer. The method for preparing the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 can be, for example, a method in which the monofunctional radical polymerizable monomer, the photopolymerization initiator, the crosslinking agent, the amine compound, and additives added as necessary are mixed using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.
[0112] The ultraviolet-curable pressure-sensitive adhesive composition of the second invention is prepared by coating the ultraviolet-curable pressure-sensitive adhesive composition on a substrate, and then applying the composition at a wavelength of 365 nm and an illuminance of 500 mW / cm under atmospheric conditions without sealing the coated surface. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The lower limit of the reaction rate of a cured product having a thickness of 50 μm obtained by irradiating the composition so as to satisfy the above condition is 90%. The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is prepared by applying the ultraviolet-curable pressure-sensitive adhesive composition to a substrate, and then irradiating the composition at a wavelength of 365 nm and an illuminance of 500 mW / cm under atmospheric conditions without sealing the coated surface. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The preferred lower limit of the reaction rate of a cured product having a thickness of 50 μm obtained by irradiating the material in such a manner as to satisfy the above condition is 90%. As the substrate, a PET film (release PET film) with a release treatment on the surface is preferably used. The above conditions are that after the ultraviolet-curable pressure-sensitive adhesive composition is coated on the substrate, the coated surface is irradiated with ultraviolet light in the presence of oxygen without covering it with a separator. Therefore, the reaction rate of the cured product reflects the ultraviolet reactivity in the presence of oxygen. Since the reaction rate of the cured product is 90% or more, it can be said that the reactivity to ultraviolet light in the presence of oxygen is sufficiently high, making it possible to apply a method in which the ultraviolet-curable pressure-sensitive adhesive composition is printed in a desired shape and then bonded to an adherend. The lower limit of the reaction rate of the cured product in the ultraviolet-curable pressure-sensitive adhesive composition of invention 2 is preferably 92%, more preferably 94%. The lower limit of the reaction rate of the cured product in the ultraviolet-curable pressure-sensitive adhesive composition of invention 1 is more preferably 91%, still more preferably 93%. In addition, the higher the reaction rate of the cured product, the more preferable it is, but the practical upper limit is 99%.
[0113] Specifically, the reaction rate of the cured product can be measured, for example, according to the following procedure. That is, first, the ultraviolet-curable pressure-sensitive adhesive composition is coated on a release PET film as a substrate, and then, without sealing the coated surface, it is irradiated with ultraviolet light at a wavelength of 365 nm and an illuminance of 500 mW / cm under atmospheric conditions using an ultraviolet irradiation device. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By simultaneously irradiating the ultraviolet-curable pressure-sensitive adhesive composition with the light beams in such a manner that the ultraviolet-curable pressure-sensitive adhesive composition is cured, a cured product having a thickness of 50 μm is obtained. Approximately 0.3 g of the obtained cured product is placed on an aluminum pan, and a mixed solvent containing THF:acetone:ethanol in a mass ratio of 8:1:1 is gently added so that the cured product sample does not scatter, and the sample is allowed to swell for about 2 hours. The sample is then dried at 110°C for 30 minutes, 170°C for 1 hour, and 190°C for 30 minutes. The mass of the aluminum pan and the dried sample after drying are then weighed, and the reaction rate of the cured product is calculated using the following formula. Reaction rate (%) = (total mass of aluminum pan and sample after drying - mass of aluminum pan before drying) / (mass of sample before swelling) x 100
[0114] In the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2, the upper limit of the temperature at which the loss tangent is maximized in a temperature range of 50°C or less (hereinafter also referred to as the "glass transition temperature of the cured product") in a viscoelasticity chart obtained by performing dynamic viscoelasticity measurement on the cured product under the conditions of a shear method, a measurement temperature of -70°C to 200°C, and a frequency of 1 Hz is 20°C. Since the glass transition temperature of the cured product is 20°C or less, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 has excellent adhesion and retention performance after curing. The upper limit of the glass transition temperature of the cured product in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 is preferably 15°C, more preferably 10°C. The ultraviolet-curable pressure-sensitive adhesive composition of the first invention can be prepared by coating the ultraviolet-curable pressure-sensitive adhesive composition on a substrate, and then applying the composition to a substrate without sealing the coated surface at a wavelength of 365 nm and an illuminance of 500 mW / cm under atmospheric conditions.2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The preferred lower limit of the glass transition temperature of the cured product having a thickness of 50 μm obtained by irradiating the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is −40° C., and the preferred upper limit is 20° C. When the glass transition temperature of the cured product is within this range, the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 has better adhesion and retention performance after curing. The more preferred lower limit of the glass transition temperature of the cured product in the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is −20° C., and the more preferred upper limit is 15° C.
[0115] Specifically, the glass transition temperature of the cured product can be measured, for example, according to the following procedure. That is, first, a dynamic viscoelasticity measurement is performed on a cured product obtained in the same manner as in the reaction rate measurement, using a dynamic viscoelasticity measuring device under the following conditions to obtain a viscoelasticity chart. In the obtained viscoelasticity chart, the tan δ peak temperature in a temperature range of 50° C. or less can be determined as the glass transition temperature. As the dynamic viscoelasticity measuring device, for example, DVA-200 (manufactured by IT Measurement and Control Co., Ltd.) can be used. <Condition> Shear Method Measurement temperature: -70℃~200℃ Heating rate: 1℃ / min Distortion: 0.1% Frequency: 1Hz
[0116] In the ultraviolet-curable pressure-sensitive adhesive composition of invention 2, the lower limit of the gel fraction of the cured product is 20% by mass, and the upper limit is 80% by mass. When the gel fraction of the cured product is within the above range, the ultraviolet-curable pressure-sensitive adhesive composition of invention 2 has excellent adhesion and retention performance after curing. In the ultraviolet-curable pressure-sensitive adhesive composition of invention 2, the lower limit of the gel fraction of the cured product is preferably 30% by mass, more preferably 40% by mass, and the upper limit is preferably 75% by mass, more preferably 70% by mass. The ultraviolet-curable pressure-sensitive adhesive composition of the present invention 1 is prepared by coating the ultraviolet-curable pressure-sensitive adhesive composition on a substrate, and then applying the composition at a wavelength of 365 nm and an illuminance of 500 mW / cm under atmospheric conditions without sealing the coated surface.2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 The preferred lower limit of the gel fraction of the cured product having a thickness of 50 μm obtained by irradiating the ultraviolet ray so as to satisfy the above condition is 20% by mass, and the preferred upper limit is 80% by mass. When the gel fraction of the cured product is within the above range, the ultraviolet-curable pressure-sensitive adhesive composition of the first invention has better adhesion and retention performance after curing. The more preferred lower limit of the gel fraction of the cured product in the ultraviolet-curable pressure-sensitive adhesive composition of the first invention is 30% by mass, and the more preferred upper limit is 70% by mass.
[0117] Specifically, the gel fraction of the cured product can be measured, for example, according to the following procedure. That is, first, 0.15 g of the cured product obtained in the same manner as in the reaction rate measurement was weighed into a glass bottle, and then immersed in 30 g of tetrahydrofuran and shaken at 23° C. for 36 hours. Next, the cured product was removed through a 200 mesh filter and dried by heating at 110° C. for 1 hour. The mass of the cured product was then measured, and the gel fraction was calculated using the following formula. Gel fraction (mass%) = (W2 / W1) x 100 W1: Mass of the cured product before immersion in tetrahydrofuran at 23°C W2: Mass of the cured product after immersion in tetrahydrofuran at 23°C, removal, and drying
[0118] The ultraviolet-curable adhesive composition of the present invention 1 is used for printing. The ultraviolet-curable adhesive composition of the present invention 2 is preferably used for printing. If an adhesive layer is formed by applying a desired pattern on an adherend (substrate) by printing, there is an advantage that the cutting process can be omitted compared to the case where an adhesive of a desired shape is obtained by cutting a sheet-like adhesive just before lamination. As a result, it is possible to suppress the generation of waste and reduce the environmental load. In addition, since lamination without gaps is possible by printing, the composition has excellent waterproof and dustproof properties.
[0119] Examples of the method for printing the ultraviolet-curable pressure-sensitive adhesive composition of invention 1 include screen printing, stencil printing, reverse offset printing, etc. Among these, screen printing is preferably used. Examples of methods for applying the ultraviolet-curable pressure-sensitive adhesive composition of the present invention 2 include gravure printing, flexographic printing, slot die coating, knife coating, inkjet printing, spray coating, spin coating, screen printing, stencil printing, reverse offset printing, etc. Among these, screen printing, stencil printing, and reverse offset printing are preferably used, and screen printing is more preferably used.
[0120] The ultraviolet-curable adhesive composition of the present invention is cured by irradiation with ultraviolet light to form an adhesive layer, and the method of use may be to form an adhesive layer on a substrate (separator) to prepare an adhesive sheet that can be transferred to an adherend, or to form an adhesive layer directly on an adherend. In the method of forming an adhesive layer directly on an adherend, the number of times of lamination can be minimized and air bubbles can be prevented from entering the interface during lamination. On the other hand, in the method of forming an adhesive layer on a substrate (separator), the adhesive layer is placed on the adherend by transfer, so there is an advantage that there are few restrictions on construction.
[0121] The present invention also provides a method for producing a laminate, which includes a step of applying the ultraviolet-curable pressure-sensitive adhesive composition of the present invention onto a first adherend and exposing the composition to light to form an adhesive layer, and a step of attaching a second adherend onto the adhesive layer, the method for applying the ultraviolet-curable pressure-sensitive adhesive composition being screen printing, stencil printing, or reverse offset printing, and in which the ultraviolet-curable pressure-sensitive adhesive composition is applied entirely or partially onto the first adherend.
[0122] Examples of the material of the first adherend and the second adherend include metals such as stainless steel and aluminum, resins, etc. Among them, the first adherend and the second adherend are preferably substrates that have been subjected to a release treatment, and more preferably substrates that have been subjected to a release treatment and an antistatic treatment.
[0123] From the viewpoint of suppressing the generation of waste and reducing the environmental load, in the method for producing a laminate of the present invention, it is preferable that the ultraviolet-curable pressure-sensitive adhesive composition of the present invention is partially coated on the first adherend.
[0124] The thickness of the adhesive layer is preferably 30 μm or more. By having a thickness of the adhesive layer of 30 μm or more, sufficient adhesion can be obtained. The thickness of the adhesive layer is more preferably 50 μm or more. In addition, from the viewpoint of responding to the trend toward thinner electronic devices, the thickness of the adhesive layer is preferably 1000 μm or less, and more preferably 500 μm or less. Effect of the Invention
[0125] According to the present invention, it is possible to provide an ultraviolet-curable pressure-sensitive adhesive composition having excellent ultraviolet curability in the presence of oxygen, waterproofness and dustproofness, and shape stability after printing, and an ultraviolet-curable pressure-sensitive adhesive composition having excellent curability when irradiated with high-intensity ultraviolet light in the presence of oxygen, and excellent adhesiveness and retention performance after curing. Furthermore, according to the present invention, it is possible to provide a method for producing a laminate using the ultraviolet-curable pressure-sensitive adhesive composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0126] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0127] (Examples 1-1 to 1-35, Comparative Examples 1-1 to 1-4) According to the compounding ratios shown in Tables 1 to 4, each material was mixed with a planetary mixer (Thinky Corporation, "Awatori Rentaro") to obtain ultraviolet-curable pressure-sensitive adhesive compositions of Examples 1-1 to 1-35 and Comparative Examples 1-1 to 1-4. Details of the materials indicated by abbreviations in Tables 1 to 4 are as follows. (Radical polymerizable monomer) CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai, no hydrogen bonded to heteroatom) CHCMA: N-(4-carboxycyclohexylmethyl)maleimide (Seiko Chemical Co., Ltd., has a structure in which hydrogen is bonded to a heteroatom) HPM: 4-hydroxyphenylmaleimide (Seiko Chemical Co., Ltd., has a structure in which hydrogen is bonded to a heteroatom) NVC: N-vinyl-ε-caprolactam (Tokyo Chemical Industry Co., Ltd.) M-140: N-Acryloyloxyethylhexahydrophthalimide (manufactured by Toagosei Co., Ltd.) NOAA: n-octyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) CBA: Ethyl carbitol acrylate (Osaka Organic Chemical Industry Co., Ltd., "Viscoat #190", contains ether bonds) 4-HBA: 4-hydroxybutyl acrylate (Mitsubishi Chemical) Viscoat #200: Cyclic trimethylolpropane formal acrylate (Osaka Organic Chemical Industry Co., Ltd.) MEDOL-10: (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl acrylate (Osaka Organic Chemical Industry Co., Ltd., contains ether bonds) Viscoat #216: 2-butylcarbamoyloxyethyl acrylate (Osaka Organic Chemical Industry, containing amide bonds) · UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) (Photopolymerization initiator) Omnirad 184: 1-Hydroxycyclohexyl phenyl ketone (IGM Resins, cleavage-type photoinitiator) Omnirad TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (IGM Resins, cleavage-type photoinitiator) Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (IGM Resins, cleavage-type photoinitiator) Esacure TZT: A mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone (manufactured by IGM Resins, a hydrogen abstraction type photopolymerization initiator) Omnirad 4MBZ: 4-Methylbenzophenone (manufactured by IGM Resins, hydrogen abstraction type photopolymerization initiator) Omnipol TP: Ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate polymer (IGM Resins, polymeric photoinitiator) Omnipol 910: Polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butanoylphenyl)piperazine)propionate (IGM Resins, polymeric photoinitiator) (Amine compounds) Eversorb 93: 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidinyl) decanedioate (manufactured by Everlight Chemical, no hydrogen bonded to heteroatom) Adeka STAB LA-72: Bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate (ADEKA, no hydrogen bonded to heteroatom) (tackifier) KE-359: Rosin resin (manufactured by Arakawa Chemical Industries Co., Ltd.) D-6011: Rosin resin (manufactured by Arakawa Chemical Industries Co., Ltd.) (Thickener) ·LA2140: Acrylic block copolymer (Kuraray, thermoplastic resin) FBP-009: Styrene-acrylic block copolymer (Fujikura Chemical Industries, thermoplastic resin) Acrylic polymer A: Synthesized using the method described below (thermoplastic resin) Disparlon 3500: Polyether phosphate ester (Kusumoto Chemicals, polymeric thixotropy regulator) Aerosil R805: Fumed silica (manufactured by Nippon Aerosil Co., Ltd., solid thickener) (Crosslinking agent) · Coronate L: Toluene diisocyanate (manufactured by Tosoh Corporation)
[0128] (Acrylic Polymer A) In a 2L separable flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube, 75 parts by mass of butyl acrylate, 25 parts by mass of 2-ethylhexyl acrylate, 3 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 300 parts by mass of ethyl acetate as a polymerization solvent were added. Next, nitrogen gas was blown in for 30 minutes to replace the atmosphere in the reaction vessel with nitrogen, and the reaction vessel was heated to 80°C while stirring. After 30 minutes, 0.5 parts by mass of t-butylperoxy-2-ethylhexanoate (1-hour half-life temperature: 92.1°C, 10-hour half-life temperature: 72.1°C) was diluted with 5 parts by mass of ethyl acetate as a polymerization initiator, and the obtained polymerization initiator solution was added dropwise to the reaction vessel over 6 hours. After that, the mixture was further reacted at 80°C for 6 hours, and then the reaction liquid was cooled to obtain an acrylic polymer solution. The obtained acrylic polymer solution was diluted with ethyl acetate to obtain a solution with a solid content of 20% by mass. The obtained solution was then applied onto a release PET film using a coater so that the thickness after drying would be 100 μm, and dried at 80° C. for 1 hour and at 110° C. for 1 hour to obtain acrylic polymer A.
[0129] (Comparative Examples 1-5) 100 parts by mass of the obtained acrylic polymer A was dissolved in 50 parts by mass of toluene. 20 parts by mass of a rosin-based resin (manufactured by Arakawa Chemical Industries, Ltd., "KE-359") was added as a tackifier to the obtained solution, and the solution was stirred to dissolve. Then, 2 parts by mass of toluene diisocyanate (manufactured by Tosoh Corporation, "Coronate L") was added as a crosslinking agent, and the mixture was stirred to obtain an ultraviolet-curable adhesive composition.
[0130] (Viscosity and thixotropic index at 25°C) The viscosity of the obtained ultraviolet-curable adhesive composition was measured at 25°C and 10 rpm using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., "TV-22") and an appropriate cone plate according to the composition. The viscosity of the obtained ultraviolet-curable adhesive composition was also measured at 25°C and 1 rpm, and the viscosity measured at 1 rpm was divided by the viscosity measured at 10 rpm to obtain the thixotropic index (Ti value). The results are shown in Tables 1 to 4.
[0131] (Reaction rate of the cured product) The obtained ultraviolet-curable pressure-sensitive adhesive composition was applied onto a release PET film (Nippa Corporation, "1-E", thickness 50 μm) using an applicator. Next, without sealing the upper surface of the coating, the composition was cured in an atmospheric environment using a batch-type UV LED curing device (CSS Corporation, "UV-LED PROCESSOR LSS-61") at a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product having a thickness of 50 μm was obtained by irradiating the film so as to obtain a thickness of 50 μm. Thereafter, the surface facing the atmosphere was sealed with a release PET film (manufactured by Nippa Corporation, "1-C", thickness 38 μm) to obtain a laminate. Then, both release films were peeled off from the laminate, and about 0.3 g of the cured product of the ultraviolet-curable adhesive composition was placed on an aluminum pan with a diameter of 10 cm and a height of 1 cm, and a mixed solvent containing THF: acetone: ethanol in a mass ratio of 8:1:1 was gently added so that the cured sample would not scatter, and the sample was allowed to swell for about 2 hours. Then, the sample was dried at 110°C for 30 minutes, at 170°C for 1 hour, and at 190°C for 30 minutes. The masses of the aluminum pan and the dried sample after drying were weighed, and the reaction rate of the cured product was calculated using the following formula. The results are shown in Tables 1 to 4. Reaction rate (%) = (total mass of aluminum pan and sample after drying - mass of aluminum pan before drying) / (mass of sample before swelling) x 100
[0132] (Gel fraction of cured product) Both release films were peeled off from the laminate obtained in the same manner as in "(Reaction rate of cured product)" above, and 0.15 g of the cured product of the ultraviolet-curable pressure-sensitive adhesive composition was weighed into a glass bottle, which was then immersed in 30 g of tetrahydrofuran and immersed with shaking at 23°C for 36 hours. The cured product was then removed through a 200-mesh filter and dried by heating at 110°C for 1 hour. The mass of the cured product was then measured, and the gel fraction was calculated using the following formula. The results are shown in Tables 1 to 4. Gel fraction (mass%) = (W2 / W1) x 100 W1: Mass of the cured product before immersion in tetrahydrofuran at 23°C W2: Mass of the cured product after immersion in tetrahydrofuran at 23°C, removal, and drying
[0133] (Glass transition temperature of the cured product) Both release films were peeled off from the laminate obtained in the same manner as in "(Reaction rate of the cured product)" above, and the cured product of the ultraviolet-curable pressure-sensitive adhesive composition was laminated to a thickness of 1 mm, which was then attached to a jig and subjected to dynamic viscoelasticity measurement under the following conditions using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") to obtain a viscoelasticity chart. The tan δ peak temperature in the obtained viscoelasticity chart was determined as the glass transition temperature. The results are shown in Tables 1 to 4. <Condition> Shear Method Measurement temperature: -70~200℃ Heating rate: 1℃ / min Distortion: 0.1% Frequency: 1Hz
[0134] <Evaluation> The ultraviolet-curable pressure-sensitive adhesive compositions obtained in Examples 1-1 to 1-35 and Comparative Examples 1-1 to 1-5 were evaluated as follows. The results are shown in Tables 1 to 4.
[0135] (180° peel adhesive strength) Each of the obtained ultraviolet-curable pressure-sensitive adhesive compositions was applied to the inner treated surface of an easily adhesive polyester film ("Cosmoshine A4100" manufactured by Toyobo Co., Ltd.) with an applicator. Thereafter, without sealing the coated surface, the coated surface was cured in an atmospheric environment using a batch-type UV LED curing device ("UV-LED PROCESSOR LSS-61" manufactured by CSS Co., Ltd.) with a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product with a thickness of 50 μm was obtained by irradiating the film so that the thickness of the film was 50 μm. The illuminance and the accumulated light quantity were measured using an ultraviolet irradiation meter UVR-T2 and a light receiving unit UD-T36T2 (manufactured by TOPCON). Next, the air surface was sealed with a release PET film (manufactured by Nippa, "1-C", thickness 38 μm), and the laminated film was cut to a width of 25 mm and a length of 200 mm (adhering surface 20 mm x 125 mm) to prepare a laminated film. After that, the release PET film was peeled off from the laminated film, and the exposed surface was attached to a SUS substrate and pressed by moving a 2 kg roller back and forth once to obtain a test specimen. The test specimen was stored in a 25°C environment for 24 hours, and the 180° peel adhesive strength was measured by performing a 180° peel at a speed of 300 mm / min using a universal testing machine (manufactured by A&D, "Tensilon RTI-1310").
[0136] (Printability (shape stability after printing)) (Screen printing) To 100 parts by mass of the obtained ultraviolet-curable adhesive composition, 1 part by mass of KS-66 (manufactured by Shin-Etsu Chemical Co., Ltd.) was added as an antifoaming agent to obtain a screen printable composition. The ultraviolet-curable adhesive composition obtained in Example 1-34 was used as a screen printable composition without adding an antifoaming agent. The obtained screen printable composition was screen-printed by applying a pattern to the inner treated surface of an easy-adhesive polyester film (manufactured by Toyobo Co., Ltd., "Cosmoshine A4100") using a screen printer (manufactured by SERIA Co., Ltd., "SSA-PC560E"). A pattern-treated 80-mesh printing plate was used as the screen printing plate. The shape of the opening of the screen printing plate was a square with a line width of 1.5 mm, and the dimensions inside the line were a square with one side of 21.5 mm. One minute after printing, the coating surface was not sealed and the coating was cured in an atmospheric environment using a batch-type UV LED curing device (manufactured by CSS, "UV-LED PROCESSOR LSS-61") at a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the material in such a manner that the thickness of the cured product was 50 μm, The line widths of the four sides of the obtained cured product were measured using a microscope (manufactured by KEYENCE Corporation) and averaged. The rate of change of the average measured line width relative to the design line width (1.5 mm) was calculated using the following formula. Line width change rate (%) = (1 - average line width / design line width) x 100 The printability (shape stability after printing) was evaluated according to the following criteria. ◎: The absolute value of the line width change rate is less than 5% ○: When the absolute value of the line width change rate is 5% or more and less than 15% △: When the absolute value of the line width change rate is 15% or more ×: Mesh penetration was not possible or there was a hole that divided the line
[0137] (Water resistance test) The center of a 40 mm square SUS304 plate was laser cut to a 20 mm square, and the surface of the resulting frame-shaped SUS plate was mirror-polished. The polished surface was then washed with ethanol and dried to prepare the SUS adherend. The cured product prepared in the same manner as in the evaluation of "(printability)" above was attached to the polished surface of the SUS adherend, and then a PET film with a thickness of 0.05 mm was attached to the surface of the cured product opposite the SUS adherend to obtain a laminate. The obtained laminate was pressed at 45 N using a universal testing machine (manufactured by A&D Co., Ltd., "Tensilon RTI-1310") and left to stand for 48 hours in a 25°C environment. Then, a cylinder with an inner diameter of 30 mm and a height of 20 mm with packing on both sides was placed on the opposite side of the SUS adherend to the surface on which the cured product was attached. The laminate with the cylinder placed was sandwiched between acrylic plate A with an air inlet and acrylic plate B with a square hole with one side of 28 mm, and fixed with screws. At this time, the PET film with the cured product attached was made to fit inside the hole of acrylic plate B. 10 mL of water was poured into the air inlet of acrylic plate A, and an air inlet tube was connected. Pressure was applied at a rate of 7 kPa / min to introduce air, and the maximum pressure (breaking pressure) was measured just before the cured material peeled off and water began to leak out.
[0138] [Table 1]
[0139] [Table 2]
[0140] [Table 3]
[0141] [Table 4]
[0142] (Evaluation of printability (shape stability after printing) when changing printing substrate) For the ultraviolet-curable pressure-sensitive adhesive compositions obtained in Examples 1-20, 1-26, 1-29 to 1-33 and Comparative Examples 1-2 and 1-5, the same screen printing as in the evaluation of "(Printability (shape stability after printing))" above and the following stencil printing were performed on each printing substrate shown in Table 5. For the screen printing, the printability (shape stability after printing) was evaluated according to the same evaluation criteria as in the evaluation of "(Printability (shape stability after printing))" above, and for the stencil printing, the printability (shape stability after printing) was evaluated according to the following evaluation criteria. The results are shown in Table 5. Details of each printing substrate listed in Table 5 are as follows. PET film: Highly adhesive polyester film (Toyobo Co., Ltd., "Cosmoshine A4100") Release PET film: PET film with release treatment on one side (Nippa Corporation, "1-E", thickness 50μm) ·SUS-BA board: SUS304-BA board
[0143] (stencil printing) The obtained ultraviolet-curable pressure-sensitive adhesive composition was stencil-printed on each printing substrate listed in Table 5 using a screen printer (Microtec Corporation, "LABTOP-38"). The stencil plate was a 55 μm thick SUS plate, the shape of the opening was a square with a line width of 1.5 mm, and the dimensions inside the line were a square with one side of 21.5 mm. In addition, a 0.3 mm wide bridge was left by half etching to support the SUS plate part inside the pattern. One minute after printing, the coating surface was not sealed and the coating was cured in an atmospheric environment using a batch-type UV LED curing device (manufactured by CSS, "UV-LED PROCESSOR LSS-61") at a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the material in such a manner that the thickness of the cured product was 50 μm, The line widths of the four sides of the obtained cured product were measured using a microscope (manufactured by KEYENCE Corporation) and averaged. The rate of change of the average measured line width relative to the design line width (1.5 mm) was calculated using the following formula. Line width change rate = (1 - average line width / design line width) x 100 The printability (shape stability after printing) was evaluated according to the following criteria. ◎: The absolute value of the line width change rate is less than 5% ○: When the absolute value of the line width change rate is 5% or more and less than 15% △: When the absolute value of the line width change rate is 15% or more ×: When liquid could not be discharged from the opening
[0144] [Table 5]
[0145] (Examples 2-1 to 2-28, Comparative Examples 2-1 to 2-4) According to the compounding ratios shown in Tables 6 to 8, each material was mixed with a planetary mixer (Thinky Corporation, "Awatori Rentaro") to obtain each of the ultraviolet-curable pressure-sensitive adhesive compositions of Examples 2-1 to 2-28 and Comparative Examples 2-1 to 2-4. Details of the materials indicated by abbreviations in the table are as follows. (Monofunctional radical polymerizable monomer) CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai, no hydrogen bonded to heteroatom) CHCMA: N-(4-carboxycyclohexylmethyl)maleimide (Seiko Chemical Co., Ltd., has a structure in which hydrogen is bonded to a heteroatom) HPM: 4-hydroxyphenylmaleimide (Seiko Chemical Co., Ltd., has a structure in which hydrogen is bonded to a heteroatom) NVC: N-vinyl-ε-caprolactam (Tokyo Chemical Industry Co., Ltd.) M-140: N-Acryloyloxyethylhexahydrophthalimide (manufactured by Toagosei Co., Ltd.) NOAA: n-octyl acrylate (Osaka Organic Chemical Industry Co., Ltd.) CBA: Ethyl carbitol acrylate (Osaka Organic Chemical Industry Co., Ltd., "Viscoat #190", contains ether bonds) 4-HBA: 4-hydroxybutyl acrylate (Mitsubishi Chemical) Viscoat #200: Cyclic trimethylolpropane formal acrylate (Osaka Organic Chemical Industry Co., Ltd.) Viscoat #216: 2-butylcarbamoyloxyethyl acrylate (Osaka Organic Chemical Industry, containing amide bonds) IBOA: Isobornyl acrylate (manufactured by Nippon Shokubai) M-5300: ω-carboxy-polycaprolactone monoacrylate (manufactured by Toagosei Co., Ltd.) (Photopolymerization initiator) Omnirad 184: 1-Hydroxycyclohexyl phenyl ketone (IGM Resins, cleavage-type photoinitiator) Omnirad TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (IGM Resins, cleavage-type photoinitiator) Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (IGM Resins, cleavage-type photoinitiator) Esacure TZT: A mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone (manufactured by IGM Resins, a hydrogen abstraction type photopolymerization initiator) Omnirad 4MBZ: 4-Methylbenzophenone (manufactured by IGM Resins, hydrogen abstraction type photopolymerization initiator) Omnipol TP: Ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate polymer (IGM Resins, polymeric photoinitiator) Omnipol 910: Polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butanoylphenyl)piperazine)propionate (IGM Resins, polymeric photoinitiator) (Crosslinking agent) · UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.) Millionate MR200: Polymeric MDI (manufactured by Tosoh Corporation) TETRAD-X: N,N,N',N'-tetraglycidyl-m-xylylenediamine (Mitsubishi Chemical Corporation) (Amine compounds) Eversorb 93: 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidinyl) decanedioate (manufactured by Everlight Chemical, no hydrogen bonded to heteroatom) Adeka STAB LA-72: Bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate (ADEKA, no hydrogen bonded to heteroatom) (tackifier) KE-359: Rosin resin (manufactured by Arakawa Chemical Industries Co., Ltd.) D-6011: Rosin resin (manufactured by Arakawa Chemical Industries Co., Ltd.) (Thickener) ·LA2140: Acrylic block copolymer (Kuraray, thermoplastic resin) FBP-009: Styrene-acrylic block copolymer (Fujikura Chemical Industries, thermoplastic resin) Acrylic polymer A: Synthesized using the method described below (thermoplastic resin) Disparlon 3500: Polyether phosphate ester (Kusumoto Chemicals, polymeric thixotropy regulator) Aerosil R805: Fumed silica (manufactured by Nippon Aerosil Co., Ltd., solid thickener)
[0146] (Acrylic Polymer A) In a 2L separable flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube, 75 parts by mass of butyl acrylate, 25 parts by mass of 2-ethylhexyl acrylate, 3 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 300 parts by mass of ethyl acetate as a polymerization solvent were added. Next, nitrogen gas was blown in for 30 minutes to replace the atmosphere in the reaction vessel with nitrogen, and the reaction vessel was heated to 80°C while stirring. After 30 minutes, 0.5 parts by mass of t-butylperoxy-2-ethylhexanoate (1-hour half-life temperature: 92.1°C, 10-hour half-life temperature: 72.1°C) was diluted with 5 parts by mass of ethyl acetate as a polymerization initiator, and the obtained polymerization initiator solution was added dropwise to the reaction vessel over 6 hours. After that, the mixture was further reacted at 80°C for 6 hours, and then the reaction liquid was cooled to obtain an acrylic polymer solution. The obtained acrylic polymer solution was diluted with ethyl acetate to obtain a solution with a solid content of 20% by mass. The obtained solution was then applied onto a release PET film using a coater so that the thickness after drying would be 100 μm, and dried at 80° C. for 1 hour and at 110° C. for 1 hour to obtain acrylic polymer A.
[0147] (Reaction rate of the cured product) The obtained ultraviolet-curable pressure-sensitive adhesive composition was applied onto a release PET film (manufactured by Nippa Corporation, "1-E", thickness 50 μm) using an applicator. Then, using a batch-type UV LED curing device (manufactured by CSS, "UV-LED PROCESSOR LSS-61"), the composition was cured with a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product having a thickness of 50 μm was obtained by irradiating the composition so as to obtain a laminate. The surface facing the atmosphere was then sealed with a release PET film (manufactured by Nippa Corporation, "1-C", thickness 38 μm) to obtain a laminate. For the ultraviolet-curable adhesive composition obtained in Example 2-16, the laminate was aged at 40° C. for 48 hours after the laminate was obtained. For the ultraviolet-curable adhesive composition obtained in Example 2-17, the laminate was aged at 40° C. for 48 hours after the laminate was obtained. Then, both release films were peeled off from the laminate, and about 0.3 g of the cured product of the ultraviolet-curable adhesive composition was placed on an aluminum pan with a diameter of 10 cm and a height of 1 cm, and a mixed solvent containing THF: acetone: ethanol in a mass ratio of 8: 1: 1 was gently added so that the cured sample would not scatter, and the sample was allowed to swell for about 2 hours. Then, the sample was dried at 110°C for 30 minutes, at 170°C for 1 hour, and at 190°C for 30 minutes. The masses of the aluminum pan and the dried sample after drying were weighed, and the reaction rate of the cured product was calculated by the following formula. The results are shown in Tables 6 to 8. Reaction rate (%) = (total mass of aluminum pan and sample after drying - mass of aluminum pan before drying) / (mass of sample before swelling) x 100
[0148] (Gel fraction of cured product) Both release films were peeled off from the laminate obtained in the same manner as in "(Reaction rate of cured product)" above, and 0.15 g of the cured product of the ultraviolet-curable pressure-sensitive adhesive composition was weighed into a glass bottle, which was then immersed in 30 g of tetrahydrofuran and immersed with shaking at 23°C for 36 hours. The cured product was then removed through a 200-mesh filter and dried by heating at 110°C for 1 hour. The mass of the cured product was then measured, and the gel fraction was calculated using the following formula. The results are shown in Tables 6 to 8. Gel fraction (mass%) = (W2 / W1) x 100 W1: Mass of the cured product before immersion in tetrahydrofuran at 23°C W2: Mass of the cured product after immersion in tetrahydrofuran at 23°C, removal, and drying
[0149] (Glass transition temperature of the cured product) Both release films were peeled off from the laminate obtained in the same manner as in "(Reaction rate of cured product)" above, and the cured product of the ultraviolet-curable pressure-sensitive adhesive composition was laminated to a thickness of 1 mm, which was then attached to a jig and subjected to dynamic viscoelasticity measurement under the following conditions using a dynamic viscoelasticity measuring device (manufactured by IT Measurement & Control Co., Ltd., "DVA-200") to obtain a viscoelasticity chart. In the obtained viscoelasticity chart, the tan δ peak temperature in the temperature range of 50°C or less was determined as the glass transition temperature. The results are shown in Tables 6 to 8. <Condition> Shear Method Measurement temperature: -70~200℃ Heating rate: 1℃ / min Distortion: 0.1% Frequency: 1Hz
[0150] <Evaluation> The ultraviolet-curable pressure-sensitive adhesive compositions obtained in Examples 2-1 to 2-28 and Comparative Examples 2-1 to 2-4 were evaluated as follows. The results are shown in Tables 6 to 8.
[0151] (180° peel adhesive strength) Each of the obtained ultraviolet-curable pressure-sensitive adhesive compositions was applied to the inner treated surface of an easily adhesive polyester film ("Cosmoshine A4100" manufactured by Toyobo Co., Ltd.) with an applicator. Thereafter, without sealing the coated surface, the coated surface was cured in an atmospheric environment using a batch-type UV LED curing device ("UV-LED PROCESSOR LSS-61" manufactured by CSS Co., Ltd.) with a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 A cured product with a thickness of 50 μm was obtained by irradiating the film so that the thickness of the film was 50 μm. The illuminance and the accumulated light quantity were measured using an ultraviolet irradiation meter UVR-T2 and a light receiving unit UD-T36T2 (manufactured by TOPCON). Next, the air surface was sealed with a release PET film (manufactured by Nippa, "1-C", thickness 38 μm), and the laminated film was cut to a width of 25 mm and a length of 200 mm (adhering surface 25 mm x 125 mm) to prepare a laminated film. After that, the release PET film was peeled off from the laminated film, and the exposed surface was attached to a SUS substrate and pressed by moving a 2 kg roller back and forth once to obtain a test specimen. The test specimen was stored in a 25°C environment for 24 hours, and the 180° peel adhesive strength was measured by performing a 180° peel at a speed of 300 mm / min using a universal testing machine (manufactured by A&D, "Tensilon RTI-1310").
[0152] (retention performance) The laminate obtained in the same manner as in "(Reaction rate of the cured product)" above was cut to 25 mm x 25 mm, one of the release PET films (1-C) was peeled off, and the cured product was attached to a mirror-polished SUS substrate with a width of 25 mm, length of 100 mm, thickness of 2 mm, and a 5 mm hole at the long edge. Next, the other release PET film (1-E) was peeled off, and the mirror-polished surface of a similar SUS substrate was attached to the exposed cured product surface, and then the substrate was pressed at 215 N using a universal testing machine (A&D Co., Ltd., "Tensilon RTI-1310") and left to stand for 48 hours in an environment of 25°C to obtain a test specimen. The obtained test piece was hung using an S-hook, and further, a 500 g weight was hung from the lower SUS substrate. This was left at 25° C., and the time until the weight fell was measured, and the retention performance was evaluated according to the following criteria. ◎: The weight did not fall even after 24 hours. ○: The time it took for the weight to fall was more than 12 hours but less than 24 hours. △: The time it took for the weight to fall was more than 1 hour but less than 12 hours. ×: The time it took for the weight to fall was less than 1 hour.
[0153] (Printability) (1) Coating method (1-1) Spin Coating (Examples 2-1 to 2-19 and Comparative Examples 2-1 to 2-4) 0.5 mL of each of the obtained ultraviolet-curable adhesive compositions was dropped onto a 50 mm × 50 mm aluminum substrate, and coated at 5,000 rpm for 10 s using a spin coater ("MSB-150" manufactured by Mikasa Co., Ltd.) to prepare a thin layer. Next, a batch-type UV LED curing device ("UV-LED PROCESSOR LSS-61" manufactured by CSS Co., Ltd.) was used to apply a 365 nm wavelength, 500 mW / cm illuminance coating. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 This was repeated until the thickness of the cured product reached 50 μm. (1-2) Applicator (Examples 2-20 to 2-26, 2-28) The obtained ultraviolet-curable pressure-sensitive adhesive composition was applied onto a release PET film (Nippa Corporation's "1-E", thickness 50 μm) with an applicator. Then, using a batch-type UV LED curing device (CSS Corporation's "UV-LED PROCESSOR LSS-61"), the composition was irradiated with light having a wavelength of 365 nm and an illuminance of 500 mW / cm. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the material in such a manner that the thickness of the cured product was 50 μm, (1-3) Screen printing (Example 2-27) Furthermore, 1 part by mass of KS-66 (manufactured by Shin-Etsu Chemical Co., Ltd.) was added as a defoamer to 100 parts by mass of the obtained ultraviolet-curable pressure-sensitive adhesive composition to obtain a screen-printable composition. The obtained screen-printable composition was screen-printed by applying a pattern to the inner treated surface of an easily adhesive polyester film (manufactured by Toyobo Co., Ltd., "Cosmoshine A4100") using a screen printer (manufactured by SERIA, "SSA-PC560E"). A pattern-treated 80-mesh printing plate was used as the screen printing plate. Next, a batch-type UV LED curing device (manufactured by CSS, "UV-LED PROCESSOR LSS-61") was used to apply a 365 nm wavelength and 500 mW / cm illuminance. 2 of ultraviolet light, with an irradiation dose of 3000mJ / cm 2 By irradiating the material in such a manner that the thickness of the cured product was 50 μm,
[0154] (2) Evaluation of printability The resulting cured products were visually inspected and the printability was evaluated according to the following criteria. ○: When a cured product with uniform thickness and surface smoothness was obtained ×: Uneven thickness, surface irregularities or repelling
[0155] [Table 6]
[0156] [Table 7]
[0157] [Table 8] [Industrial Applicability]
[0158] According to the present invention, it is possible to provide an ultraviolet-curable pressure-sensitive adhesive composition having excellent ultraviolet curability in the presence of oxygen, waterproofness and dustproofness, and shape stability after printing, and an ultraviolet-curable pressure-sensitive adhesive composition having excellent curability when irradiated with high-intensity ultraviolet light in the presence of oxygen, and excellent adhesiveness and retention performance after curing. Furthermore, according to the present invention, it is possible to provide a method for producing a laminate using the ultraviolet-curable pressure-sensitive adhesive composition.
Claims
1. An ultraviolet-curable pressure-sensitive adhesive composition for use in printing, comprising: Contains a radical polymerizable monomer, a photopolymerization initiator, and a thickener, The radical polymerizable monomer includes a compound having a cyclic structure containing a nitrogen atom, The viscosity measured using an E-type viscometer at 25°C and 10 rpm is 3 Pa·s or more and 100 Pa·s or less.
1. An ultraviolet-curable pressure-sensitive adhesive composition comprising:
2. The ultraviolet-curable pressure-sensitive adhesive composition is coated on a substrate, and the coated surface is not sealed, and the coating is irradiated with light having a wavelength of 365 nm and an illuminance of 500 mW / cm in an atmospheric environment. 2 of ultraviolet light with an irradiation dose of 3000 mJ / cm 2 2. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, wherein the reaction rate of a cured product having a thickness of 50 μm is 90% or more by irradiation so as to obtain a cured product having a thickness of 50 μm.
3. 3. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, wherein the compound having a cyclic structure containing a nitrogen atom comprises at least one selected from the group consisting of radically polymerizable monomers having a lactam structure and maleimide derivatives.
4. The compound having a cyclic structure containing a nitrogen atom includes the maleimide derivative. the maleimide derivative has a content of at least 50 mass% of a maleimide derivative not having a structure in which hydrogen is bonded to a heteroatom, or a content of a maleimide derivative having a structure in which hydrogen is bonded to a heteroatom, relative to 100 mass parts of the radical polymerizable monomer, of 10 parts by mass or less; 4. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 3, wherein the content of the maleimide derivative is 0.1 parts by mass or more and 20 parts by mass or less in 100 parts by mass of the radical polymerizable monomer.
5. the compound having a cyclic structure containing a nitrogen atom includes the radical polymerizable monomer having a lactam structure, 4. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 3, wherein the content of the radical polymerizable monomer having a lactam structure is 10 parts by mass or more and 60 parts by mass or less in 100 parts by mass of the radical polymerizable monomer.
6. The radical polymerizable monomer contains 20% by mass or more of a monomer capable of serving as a hydrogen donor, The photopolymerization initiator includes at least one selected from the group consisting of a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator, The ultraviolet-curable pressure-sensitive adhesive composition further contains an amine compound, The amine compound has a content of 50 mass% or more of an amine compound that does not have a structure in which hydrogen is bonded to a heteroatom, 6. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, wherein the content of the amine compound is 0.1 parts by mass or more and 10 parts by mass or less in a total of 100 parts by mass of the ultraviolet-curable pressure-sensitive adhesive composition excluding the photopolymerization initiator.
7. 7. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, wherein the radical polymerizable monomer comprises a polyfunctional (meth)acrylic monomer.
8. 8. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, wherein the thickener comprises at least one selected from the group consisting of a thermoplastic resin, a polymeric thixotropy regulator, and a solid thickener.
9. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 8 , wherein the thickener contains the thermoplastic resin, and the thermoplastic resin contains a (meth)acrylic copolymer.
10. The ultraviolet-curable pressure-sensitive adhesive composition is coated on a substrate, and the coated surface is not sealed, and the coating is irradiated with light having a wavelength of 365 nm and an illuminance of 500 mW / cm in an atmospheric environment. 2 of ultraviolet light with an irradiation dose of 3000 mJ / cm 2 The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein the glass transition temperature of a cured product having a thickness of 50 μm obtained by irradiating the composition so as to satisfy the above condition is −40° C. or higher and 20° C. or lower.
11. The ultraviolet-curable pressure-sensitive adhesive composition is coated on a substrate, and the coated surface is not sealed, and the coating is irradiated with light having a wavelength of 365 nm and an illuminance of 500 mW / cm in an atmospheric environment. 2 of ultraviolet light with an irradiation dose of 3000 mJ / cm 2 The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1 , wherein the gel fraction of a cured product having a thickness of 50 μm obtained by irradiating the composition so as to satisfy the above condition is from 20% by mass to 80% by mass.
12. The composition contains a monofunctional radical polymerizable monomer, a photopolymerization initiator, and a crosslinking agent having two or more reactive functional groups in one molecule, The monofunctional radical polymerizable monomer includes a compound having a cyclic structure containing a nitrogen atom, The ultraviolet-curable pressure-sensitive adhesive composition is coated on a substrate, and the coated surface is not sealed, and the coating is irradiated with light having a wavelength of 365 nm and an illuminance of 500 mW / cm in an atmospheric environment. 2 of ultraviolet light with an irradiation dose of 3000 mJ / cm 2 The reaction rate of a cured product having a thickness of 50 μm obtained by irradiating the material in such a manner as to satisfy the above condition is 90% or more, The gel fraction of the cured product is 20% by mass or more and 80% by mass or less, The cured product is subjected to dynamic viscoelasticity measurement under the conditions of a shear method, a measurement temperature of −70° C. to 200° C., and a frequency of 1 Hz. In the obtained viscoelasticity chart, the temperature at which the loss tangent reaches a maximum value in a temperature range of 50° C. or less is 20° C. or less.
1. An ultraviolet-curable pressure-sensitive adhesive composition comprising:
13. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 12, wherein the compound having a cyclic structure containing a nitrogen atom comprises at least one selected from the group consisting of monofunctional radically polymerizable monomers having a lactam structure and maleimide derivatives.
14. The compound having a cyclic structure containing a nitrogen atom includes the maleimide derivative. the maleimide derivative has a content of at least 50 mass% of a maleimide derivative not having a structure in which hydrogen is bonded to a heteroatom, or a content of a maleimide derivative having a structure in which hydrogen is bonded to a heteroatom, relative to 100 mass parts of the monofunctional radical polymerizable monomer, of 10 parts by mass or less; The ultraviolet-curable pressure-sensitive adhesive composition according to claim 13, wherein the content of the maleimide derivative is 0.1 parts by mass or more and 20 parts by mass or less in 100 parts by mass of the monofunctional radically polymerizable monomer.
15. the compound having a cyclic structure containing a nitrogen atom includes the monofunctional radical polymerizable monomer having a lactam structure, The ultraviolet-curable pressure-sensitive adhesive composition according to claim 13, wherein the content of the monofunctional radically polymerizable monomer having a lactam structure is 10 parts by mass or more and 60 parts by mass or less in 100 parts by mass of the monofunctional radically polymerizable monomer.
16. The monofunctional radical polymerizable monomer contains 20% by mass or more of a monomer capable of serving as a hydrogen donor, The photopolymerization initiator includes at least one selected from the group consisting of a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator, The ultraviolet-curable pressure-sensitive adhesive composition further contains an amine compound, The amine compound has a content of 50 mass% or more of an amine compound that does not have a structure in which hydrogen is bonded to a heteroatom, The ultraviolet-curable pressure-sensitive adhesive composition according to claim 12, 13, 14 or 15, wherein the content of the amine compound is 0.5 parts by mass or more and 8.0 parts by mass or less per 100 parts by mass of the ultraviolet-curable pressure-sensitive adhesive composition excluding the photopolymerization initiator.
17. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 16, wherein the monomer capable of serving as a hydrogen donor is a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.
18. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 17, wherein the monofunctional radically polymerizable monomer contains 30 mass% or more of a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.
19. 19. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 12, 13, 14, 15, 16, 17 or 18, wherein the crosslinking agent has, as the reactive functional group, two or more of at least one selected from the group consisting of an isocyanate group, an epoxy group, an aldehyde group, a hydroxyl group, an amino group, a (meth)acryloyl group, and a vinyl group in one molecule.
20. 20. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 12, further comprising a thickener.
21. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 20, wherein the thickener is at least one selected from the group consisting of a thermoplastic resin, a polymeric thixotropy regulator, and a solid thickener.
22. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, further comprising a tackifier.
23. The ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, further comprising an antifoaming agent.
24. The method includes a step of applying the ultraviolet-curable pressure-sensitive adhesive composition according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22 or 23 onto a first adherend, and exposing the composition to light to form a pressure-sensitive adhesive layer, and a step of attaching a second adherend onto the pressure-sensitive adhesive layer, The method for applying the ultraviolet-curable pressure-sensitive adhesive composition is screen printing, stencil printing, or reverse offset printing, and the ultraviolet-curable pressure-sensitive adhesive composition is applied entirely or partially onto the first adherend.
25. The method for producing a laminate according to claim 24, wherein the first adherend and the second adherend are release-treated substrates.
26. 26. The method for producing a laminate according to claim 25, wherein the first adherend and the second adherend are base materials which have been subjected to a release treatment and an antistatic treatment.
27. The method for producing a laminate according to claim 24, 25 or 26, wherein the ultraviolet-curable pressure-sensitive adhesive composition is applied partially onto the first adherend.
Citation Information
Patent Citations
Radiation-curing adhesive composition and laminate using the same
JP2013216742A
Photocurable adhesive composition
WO2016163152A1
Cited By
Monomer-based adhesive composition for picoliter-level dispensing
KR102988830B1
Solvent-free adhesive composition having oligomer for digital dispensing
KR102988834B1
Optical sheet having adhesive composition for nozzle dispensing
KR102988835B1
Adhesive film and temporary fixing material
WO2026186764A1